Adhesive sheet

By using the adhesive resin composition containing filler particles in the adhesive sheet, the problem of difficulty in peeling the adhesive tape in small electronic equipment and easy tearing of thin substrates is solved, thereby achieving high impact resistance and excellent adhesive strength.

CN119842336APending Publication Date: 2025-04-18DIC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510126430.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-12-13
Filing Date
2019-08-29
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In small electronic equipment, the existing adhesive tape is difficult to peel off in parallel due to the narrow space, and is prone to tear in the case of a thin substrate, and has insufficient impact resistance and adhesive strength.

Method used

Adhesive sheets with adhesive layer and substrate layer are used, which contain filler particles and binder resin. The content and volume ratio of filler particles are within a specific range to ensure that they can be easily peeled off in the vertical direction and are not easily teared in the case of thin substrates.

Benefits of technology

An adhesive sheet that can be easily peeled off in the vertical direction is realized, and it is not easy to tear in the case of a thin substrate, and impact resistance, shear adhesion and cut adhesion are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005260014500000141
    Figure BDA0005260014500000141
  • Figure BDA0005260014500000381
    Figure BDA0005260014500000381
  • Figure BDA0005260014500000511
    Figure BDA0005260014500000511
Patent Text Reader

Abstract

Provided is an adhesive sheet which can be easily stretched and peeled even if the stretching direction is perpendicular to the attachment surface of an object to be attached, is not easily torn even if the thickness of the base material of the adhesive sheet is thin, and has excellent impact resistance, shear adhesive strength, and cleavage adhesive strength. The present invention relates to an adhesive sheet having an adhesive layer and a base material layer, the adhesive layer containing filler particles and a binder resin, the content of the filler particles in the adhesive layer being 10-90 parts by weight per 100 parts by weight of the binder resin, the volume ratio of the filler particles to the adhesive layer being 4-40%, and the base material layer containing a binder resin and a filler particles contained in the adhesive layer being 10-90 parts by weight per 100 parts by weight of the binder resin. The pressure-sensitive adhesive sheet has a stress of 0.15-82 Mpa when the pressure-sensitive adhesive sheet is stretched by 25%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application based on the Chinese invention patent application with application number: 201980075281.8, application date: August 29, 2019, and invention name: “Adhesive Sheet”. Technical Field

[0002] The present invention relates to an adhesive sheet. Background Art

[0003] Adhesive sheets (sometimes also referred to as "adhesive tapes") are a bonding means with excellent workability and high bonding reliability, and therefore are widely used in the case of fixing components constituting electronic devices. Specifically, the adhesive tapes are used for fixing components in various industrial fields, such as fixing sheet metals constituting relatively large electronic devices such as thin-screen TVs, home appliances, and OA equipment, fixing exterior components to frames, fixing rigid components such as exterior components and batteries to relatively small electronic devices such as portable electronic terminals, cameras, and personal computers, and temporarily fixing the components, and can also be used for labeling purposes such as displaying product information.

[0004] In recent years, in the above-mentioned industrial fields, from the perspective of protecting the global environment, in order to save resources, etc., the reused or reusable parts used in the products are mostly decomposed after use and reused or reused. At this time, when using an adhesive tape, it is necessary to peel off the adhesive tape attached to the parts, but the above-mentioned adhesive tape usually has a strong adhesive force and is attached to multiple parts of the product, so the operation of peeling them off is accompanied by a lot of labor. Therefore, an adhesive tape that can be relatively easily peeled and removed when reused or reused is required. As an adhesive tape that can be easily peeled and removed, the following adhesive tape has been proposed: it has an adhesive portion and a joint portion, and the joint portion can be clamped from the adherends on both sides of the adhesive portion and stretched in a direction substantially parallel to the adhesive surface to be peeled off (see Patent Document 1). However, in the above-mentioned small electronic device, since the space between the components in the electronic device is narrow, there is a problem that it is difficult to stretch and peel the adhesive tape attached to the above space in a direction parallel to the adhesive surface.

[0005] In this regard, an adhesive tape that can be removed again by stretching it in a 30° direction relative to the adhesive surface has also been proposed (see Patent Document 2). However, in order to stretch and peel the adhesive tape attached to a narrow space, it is desired to further extend and peel it at an angle.

[0006] In addition, in order to ensure the flexibility of the adhesive tape, the thickness of the base material of the adhesive tape is thinned, and there is a problem of easy tearing due to elongation and peeling. On the other hand, if the flexibility of the adhesive tape is low, there is a problem of peeling of the adhesive tape due to the impact of the product used, especially the small electronic device falling during use. In view of the above problems, there is a proposed adhesive tape that is not damaged by tearing due to stretching operation and has impact resistance (refer to patent document 3). However, the adhesive tape of the proposal has the problem of being unable to have an angle and elongating and peeling.

[0007] Therefore, there is a strong demand for providing an adhesive tape that can not only be stretched and peeled in a direction parallel to the attachment surface of the attachment object (horizontal direction) but can also be easily stretched and peeled in a vertical direction, is not easy to tear even when the thickness of the base material of the adhesive tape is thin, and has excellent impact resistance, shear adhesion and cleavage adhesion. Prior art literature Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2015-124289 Patent Document 2: Japanese Patent Application No. 2016-504449 Patent Document 3: Japanese Patent Application Publication No. 2015-124289 Summary of the invention

[0009] The subject of the present invention is to solve the above-mentioned various problems in the past and achieve the following objectives. That is, the object of the present invention is to provide an adhesive sheet that can be easily stretched and peeled even when the stretching direction is perpendicular to the attachment surface of the attachment object, is not easy to tear even when the thickness of the substrate of the adhesive sheet is thin, and has excellent impact resistance, shear adhesion and cleavage adhesion.

[0010] Means for solving the above-mentioned problems are as follows. That is, an adhesive sheet, characterized in that it has an adhesive layer and a substrate layer, the adhesive layer contains filler particles and an adhesive resin, the content of the filler particles in the adhesive layer is 10 to 90 parts by weight relative to 100 parts by weight of the adhesive resin, the volume ratio of the filler particles to the adhesive layer is 4% to 40%, and the stress of the adhesive sheet when it is elongated by 25% is 0.15Mpa to 82Mpa.

[0011] According to the present invention, the above-mentioned various problems in the past can be solved, the above-mentioned objects can be achieved, and an adhesive sheet can be provided, which can be easily stretched and peeled even if the stretching direction is a direction perpendicular to the attachment surface of the attachment object, and is not easy to tear even when the thickness of the base material of the adhesive sheet is thin, and has excellent impact resistance, shear adhesion and cleavage adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a schematic diagram for explaining a method of attaching a pressure-sensitive adhesive sheet 1 and an acrylic plate 2 when evaluating impact resistance in Examples. Figure 2 This is a schematic explanatory diagram of a test piece prepared when evaluating impact resistance in Examples. Figure 3 This is a schematic diagram for explaining the method of setting the test piece on the U-shaped measuring table when evaluating the impact resistance in the examples. DETAILED DESCRIPTION

[0013] (Adhesive Sheet) The pressure-sensitive adhesive sheet of the present invention comprises at least a pressure-sensitive adhesive layer and a substrate layer, and may further comprise other layers as necessary.

[0014] <Adhesive layer> The adhesive layer contains at least filler particles and a binder resin, and may contain other components as necessary. The components constituting the adhesive layer are not particularly limited as long as they are contained in the adhesive layer, but are preferably contained in an adhesive composition.

[0015] <<Adhesive composition>> The adhesive composition contains at least the filler particles and the adhesive resin, and may further contain other components as necessary.

[0016] - Filler particles - By making the adhesive layer contain the filler particles, the filler particles are exposed from the adhesive layer when the adhesive sheet is stretched, thereby reducing the bonding area between the adhesive layer and the adherend. Therefore, even if the stretching direction of the adhesive sheet is a direction perpendicular to the attachment surface (hereinafter sometimes also referred to as the "adhesive surface") of the attachment object (hereinafter sometimes also referred to as the "adhesive object") (sometimes also referred to as the "90° direction"), it can be easily stretched and peeled.

[0017] The type of the filler particles is not particularly limited and can be appropriately selected within a range that does not impair the effects of the present invention, and may be inorganic filler particles or organic filler particles. These may be used alone or in combination of two or more.

[0018] Specific examples of the inorganic filler particles include aluminum hydroxide, magnesium hydroxide, aluminum oxide, silicon oxide, magnesium oxide, zinc oxide, titanium oxide, zirconium oxide, iron oxide, silicon carbide, boron nitride, aluminum nitride, titanium nitride, silicon nitride, titanium boride, carbon, nickel, copper, aluminum, titanium, gold, silver, zirconium hydroxide, basic magnesium carbonate, dolomite, hydrotalcite, calcium hydroxide, barium hydroxide, tin oxide, tin oxide hydrate, borax, zinc borate, zinc metaborate, barium metaborate, zinc carbonate, magnesium-calcium carbonate, calcium carbonate, barium carbonate, molybdenum oxide, Antimony oxide, red phosphorus, mica, clay, kaolin, talc, zeolite, wollastonite, montmorillonite, silicon dioxide (quartz, fumed silica, precipitated silica, anhydrous silicic acid, fused silica, crystalline silica, ultrafine amorphous silica, etc.), potassium titanate, magnesium sulfate, sepiolite, xonotlite, aluminum borate, barium sulfate, barium titanate, zirconium oxide, cerium, tin, indium, carbon, sulfur, tellurium, cobalt, molybdenum, strontium, chromium, barium, lead, tin oxide, indium oxide, diamond, magnesium, platinum, zinc, manganese, stainless steel, etc. Among them, aluminum hydroxide, nickel, etc. are preferred. Furthermore, the inorganic filler may be subjected to a surface treatment such as a silane coupling treatment or a stearic acid treatment in order to improve dispersibility in the binder resin.

[0019] Specific examples of the above-mentioned organic filler particles include polystyrene fillers, benzoguanamine fillers, polyethylene fillers, polypropylene fillers, silicone fillers, urea-formalin fillers, styrene / methacrylic acid copolymers, fluorine fillers, acrylic fillers, polycarbonate fillers, polyurethane fillers, polyamide fillers, epoxy resin fillers, thermosetting resin hollow fillers, etc.

[0020] As the shape of the above-mentioned filler particles, there is no particular restriction, and it can be appropriately selected according to the purpose, and can be a regular shape or an irregular shape. As a specific example of the shape of the above-mentioned filler particles, polygonal, cubic, elliptical, spherical, needle-shaped, flat, flaky, etc. can be cited. The above-mentioned filler particles of the above-mentioned shape can be used alone or in combination of two or more. In addition, it can also be a material formed by the agglomeration of the filler particles of the above-mentioned shape. Wherein, as the shape of the above-mentioned filler particles, it is preferably elliptical, spherical, polygonal. If the above-mentioned filler particles are elliptical, spherical, polygonal and other shapes, then when the above-mentioned adhesive sheet is stretched, the above-mentioned adhesive layer slides well relative to the above-mentioned adherend, even if the stretching direction of the above-mentioned adhesive sheet is 90 ° direction relative to the attachment surface of the adherend, it can also be easily stretched and peeled.

[0021] As the particle size distribution (D 90 / D 10), which is not particularly limited and can be appropriately selected according to the purpose, is preferably 2.5 to 20, more preferably 2.5 to 15, and further preferably 2.5 to 5 from the perspective of impact resistance. 90 / D 10 ) is within the above preferred range, even if the stretching direction of the adhesive sheet is 90° relative to the attachment surface of the adherend, it can be easily stretched and peeled, and even if the thickness of the substrate of the adhesive sheet is thin, it is not easy to tear, and the impact resistance, shear adhesion and splitting adhesion are excellent. On the other hand, if the particle size distribution (D 90 / D 10 ) is less than 2.5, the elongation peeling property of the above-mentioned adhesive sheet when the elongation direction is 90° relative to the attachment surface of the adherend is sometimes impaired. If it exceeds 20, the adhesive properties such as impact resistance, shear adhesion, and cleavage adhesion are sometimes impaired. The particle size distribution of the filler particles (D 90 / D 10 ) is obtained by, for example, measuring the particle size of the filler particles using a measuring machine (Microtrac) utilizing a laser diffraction scattering method and converting the result into a particle size distribution.

[0022] The volume average particle size of the filler particles is not particularly limited and can be appropriately selected according to the purpose, preferably 3 μm to 25 μm, more preferably 5 μm to 20 μm, and further preferably 5 μm to 14 μm. If the volume average particle size of the filler particles is within the preferred range, even if the elongation direction of the adhesive sheet is 90° relative to the attached surface of the adherend, it can be easily stretched and peeled, even if the thickness of the substrate of the adhesive sheet is thin, it is not easy to tear, and the impact resistance, shear adhesion and split adhesion are excellent. On the other hand, if the volume average particle size of the filler particles is less than 3 μm, it is sometimes difficult to stretch and peel when the elongation direction of the adhesive sheet is 90° relative to the attached surface of the adherend. If it exceeds 25 μm, the bonding properties such as impact resistance, shear adhesion and split adhesion are sometimes impaired. The volume average particle size of the filler particles can be measured, for example, using a measuring device (Microtrac) using a laser diffraction scattering method.

[0023] The ratio of the volume average particle size of the filler particles to the average thickness of the adhesive layer described later is not particularly limited and can be appropriately selected according to the purpose. The ratio of the volume average particle size of the filler particles represented by [volume average particle size of the filler particles / average thickness of the adhesive layer] to the average thickness of the adhesive layer is preferably 5 / 100 or more, more preferably 5 / 100 to 95 / 100, further preferably 10 / 100 to 75 / 100, and particularly preferably 20 / 100 to 60 / 100. If the above ratio is within the above preferred range, even if the elongation direction of the adhesive sheet is 90° relative to the attachment surface of the adherend, it can be easily stretched and peeled, and even if the thickness of the substrate of the adhesive sheet is thin, it is not easy to tear. In addition, if the above ratio is within the above particularly preferred range, even if the elongation direction of the adhesive sheet is 90° relative to the attached surface of the adherend, it can be easily elongated and peeled, and even if the thickness of the substrate of the adhesive sheet is thin, it is not easy to tear, and it is advantageous in terms of better bonding performance such as impact resistance, shear adhesion, and split adhesion. On the other hand, if the above ratio is less than 5 / 100, the elongation and peeling performance when the elongation direction of the adhesive sheet is 90° relative to the attached surface of the adherend is sometimes impaired, and if it exceeds 95 / 100, the bonding performance such as impact resistance, shear adhesion, and split adhesion is sometimes impaired.

[0024] The content of the filler particles in the adhesive layer is 10 to 90 parts by weight (parts by mass) relative to 100 parts by weight of the adhesive resin, preferably 15 to 50 parts by weight, and more preferably 20 to 40 parts by weight. If the content of the filler particles relative to 100 parts by weight of the adhesive resin is less than 10 parts by weight, the adhesive sheet cannot be stretched and peeled off when the elongation direction of the adhesive sheet is 90° relative to the attached surface of the adherend. In addition, the adhesive sheet is torn, and the adhesive sheet cannot be stretched and can no longer be peeled off. In addition, if the content of the filler particles relative to 100 parts by weight of the adhesive resin exceeds 90 parts by weight, sometimes the adhesive sheet does not stretch, the adhesive composition remains on the adherend, the impact resistance deteriorates, and the shear bonding force and the cleavage bonding force weaken. On the other hand, if the content of the filler particles relative to 100 parts by weight of the adhesive resin is 10 parts by weight to 90 parts by weight, the adhesive sheet can be easily stretched and peeled off even if the stretching direction is 90° relative to the attachment surface of the adherend, and is not easy to tear even when the thickness of the substrate of the adhesive sheet is thin, and has excellent impact resistance, shear adhesion and cleavage adhesion. The content of the filler particles in the adhesive layer may be appropriately adjusted when preparing the adhesive composition.

[0025] The volume ratio of the filler particles relative to the volume of the entire adhesive layer is 4% to 40%, preferably 5% to 30%, more preferably 5% to 20%, and further preferably 5% to 15%. If the volume ratio of the filler particles is less than 4%, the adhesive sheet cannot be stretched and peeled when the elongation direction is 90° relative to the attached surface of the adherend. In addition, the adhesive sheet is torn, and the adhesive sheet does not stretch and cannot be peeled off again. In addition, if the volume ratio of the filler particles exceeds 40%, sometimes the adhesive sheet does not stretch, the adhesive composition remains on the adherend, the impact resistance deteriorates, and the shear adhesion and split adhesion become weak. On the other hand, if the volume ratio of the filler particles is 4% to 40%, even if the elongation direction of the adhesive sheet is 90° relative to the attached surface of the adherend, it can be easily stretched and peeled, even if the thickness of the substrate of the adhesive sheet is thin, it is not easy to tear, and the impact resistance, shear adhesion and split adhesion are excellent. The volume ratio of the filler particles to the adhesive layer can be calculated according to the following formulas (1) to (3). Binder resin *1 Weight A(g) / Binder resin *1 Density A(g / cm 3 )=Binder resin *1 Volume A(cm 3 )···Formula (1) Weight of filler particles B (g) / density of filler particles B (g / cm 3 ) = volume of filler particles B (cm 3 )···Formula (2) The volume of filler particles B (cm 3 ) / (Binder resin *1 Volume A(cm 3 ) + volume of filler particles B (cm 3 ))×100=volume ratio of filler particles (%)···Formula (3) It should be noted that in the above formulas (1) and (3), *1 The binder resin shown may contain other components described in paragraph

[0079] described later. The above density is a value measured in accordance with JIS Z 8804.

[0026] -Binder resin- The binder resin is not particularly limited and can be appropriately selected from known materials, for example, acrylic binder resins, rubber binder resins, urethane binder resins, silicone binder resins, etc. These can be used alone or in combination of two or more. Among them, acrylic binder resins are preferred as the binder resin.

[0027] --Acrylic Binder Resin-- The acrylic binder resin is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include resins containing an acrylic polymer and, if necessary, additives such as a tackifier resin and a crosslinking agent.

[0028] The acrylic polymer can be produced, for example, by polymerizing a monomer mixture containing a (meth)acrylic monomer. As the (meth)acrylic monomer, for example, an alkyl (meth)acrylate having an alkyl group having 1 to 12 carbon atoms, etc. can be used. Specific examples of the alkyl (meth)acrylate having an alkyl group with 1 to 12 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. These may be used alone or in combination of two or more.

[0029] As the alkyl (meth)acrylate having an alkyl group having 1 to 12 carbon atoms, an alkyl (meth)acrylate having an alkyl group having 4 to 12 carbon atoms is preferably used, and an alkyl (meth)acrylate having an alkyl group having 4 to 8 carbon atoms is more preferably used. In terms of ensuring excellent adhesion to the adherend, n-butyl acrylate is particularly preferably used.

[0030] The alkyl (meth)acrylate having 1 to 12 carbon atoms is preferably used in an amount of 80 to 98.5 wt %, more preferably 90 to 98.5 wt %, based on the total amount of monomers used in the production of the acrylic polymer.

[0031] As monomers which can be used for producing the acrylic polymer, in addition to the above-mentioned monomers, a highly polar vinyl monomer can be used as needed. Examples of the highly polar vinyl monomer include (meth)acrylic monomers having a hydroxyl group, (meth)acrylic monomers having a carboxyl group, (meth)acrylic monomers having an amide group, and the like, and sulfonic acid group-containing monomers such as vinyl acetate, ethylene oxide-modified succinic acid acrylate, and 2-acrylamide-2-methylpropanesulfonic acid. These monomers may be used alone or in combination of two or more.

[0032] Specific examples of the vinyl monomer having a hydroxyl group include (meth)acrylic monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate.

[0033] The vinyl monomer having a hydroxyl group is preferably used when a resin containing an isocyanate crosslinking agent is used as the binder resin. Specifically, as the vinyl monomer having a hydroxyl group, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate are preferably used.

[0034] The vinyl monomer having a hydroxyl group is preferably used in an amount within a range of 0.01 to 1.0 wt %, more preferably 0.03 to 0.3 wt %, based on the total amount of monomers used in the production of the acrylic polymer.

[0035] Specific examples of the vinyl monomer having a carboxyl group include (meth)acrylic acid monomers such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, (meth)acrylic acid dimer, crotonic acid, and ethylene oxide-modified succinic acid acrylate. Among them, acrylic acid is preferred.

[0036] Specific examples of the vinyl group having an amide group include (meth)acrylic monomers such as N-vinylpyrrolidone, N-vinylcaprolactam, acryloylmorpholine, acrylamide, and N,N-dimethylacrylamide.

[0037] The above-mentioned high-polarity vinyl monomer is preferably used in the range of 1.5 wt % to 20 wt % relative to the total amount of monomers used in the preparation of the above-mentioned acrylic polymer, and is more preferably used in the range of 1.5 wt % to 10 wt %. Since it can form an adhesive layer that achieves a balance in cohesion, retention and adhesion, it is further preferably used in the range of 2 wt % to 8 wt %.

[0038] The method for producing the acrylic polymer is not particularly limited and can be appropriately selected from known methods according to the purpose, and examples thereof include methods of polymerizing the monomers by polymerization methods such as solution polymerization, bulk polymerization, suspension polymerization, and emulsion polymerization. Among them, the acrylic polymer is preferably produced by solution polymerization or bulk polymerization.

[0039] In the above-mentioned polymerization, if necessary, peroxide-based thermal polymerization initiators such as benzoyl peroxide and lauroyl peroxide, azo thermal polymerization initiators such as azobisisobutyronitrile, acetophenone-based photopolymerization initiators, benzoin ether-based photopolymerization initiators, benzyl ketal-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzophenone-based photopolymerization initiators, etc. can be used.

[0040] The acrylic polymer obtained by the above method preferably has a weight average molecular weight of 300,000 to 3,000,000, more preferably 500,000 to 2,500,000, as measured by gel permeation chromatography (GPC) in terms of standard polystyrene.

[0041] Here, the weight average molecular weight of the acrylic polymer measured by the GPC method is a standard polystyrene conversion value measured using a GPC apparatus (HLC-8329GPC, manufactured by Tosoh Corporation), and the measurement conditions are as follows. [Measurement conditions] Sample concentration: 0.5 wt% (tetrahydrofuran (THF) solution) Sample injection volume: 100μL Eluent: THF Flow rate: 1.0mL / min ·Measurement temperature: 40℃ Main column: TSKgel GMHHR-H (20) 2 pieces Guard column: TSKgel HXL-H Detector: Differential refractometer · Standard polystyrene molecular weight: 10,000 to 20,000,000 (manufactured by Tosoh Corporation)

[0042] As the acrylic adhesive resin, it is preferable to use an acrylic adhesive resin containing a tackifier resin in order to improve the adhesion to an adherend and the surface adhesive strength.

[0043] The tackifier resin contained in the acrylic adhesive resin is not particularly limited and can be appropriately selected according to the purpose. A tackifier resin having a softening point of 30° C. to 180° C. is preferred, and a tackifier resin having a softening point of 70° C. to 140° C. is more preferred from the perspective of forming an adhesive layer having high adhesive performance. When a (meth)acrylate tackifier resin is used, its glass transition temperature is preferably 30° C. to 200° C., and more preferably 50° C. to 160° C.

[0044] As the specific example of the tackifier resin contained in the above-mentioned acrylic acid-based binder resin, rosin-based tackifier resin, polymerized rosin-based tackifier resin, polymerized rosin ester-based tackifier resin, rosin phenolic tackifier resin, stabilized rosin ester-based tackifier resin, disproportionated rosin ester-based tackifier resin, hydrogenated rosin ester-based tackifier resin, terpene-based tackifier resin, terpene phenolic tackifier resin, petroleum resin-based tackifier resin, (methyl) acrylate ester-based tackifier resin, etc. can be enumerated. They can be used alone or in combination of more than two kinds. Wherein, the preferred polymerized rosin ester-based tackifier resin of the above-mentioned tackifier resin, rosin phenolic tackifier resin, disproportionated rosin ester-based tackifier resin, hydrogenated rosin ester-based tackifier resin, terpene phenolic tackifier resin, (methyl) acrylate ester-based resin.

[0045] The amount of the tackifier resin used is not particularly limited and can be appropriately selected according to the purpose. It is preferably used in the range of 5 to 65 parts by weight relative to 100 parts by weight of the acrylic polymer. Using it in the range of 8 to 55 parts by weight is more preferred because it is easy to ensure adhesion to the adherend.

[0046] As the acrylic adhesive resin, it is preferable to use an acrylic adhesive resin containing a crosslinking agent in order to further improve the cohesive force of the adhesive layer.

[0047] As the cross-linking agent, there is no particular limitation and it can be appropriately selected according to the purpose, for example, isocyanate cross-linking agents, epoxy cross-linking agents, metal chelate cross-linking agents, aziridine cross-linking agents, etc. can be mentioned. One of them can be used alone, or two or more of them can be used in combination. Among them, the cross-linking agent is preferably mixed after the manufacture of the acrylic acid polymer, and the type of cross-linking agent that undergoes a cross-linking reaction is more preferably an isocyanate cross-linking agent and an epoxy cross-linking agent rich in reactivity with the acrylic acid polymer.

[0048] As the above-mentioned isocyanate-based crosslinking agent, for example, toluene diisocyanate, triphenylmethane isocyanate, naphthalene-1,5-diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, trimethylolpropane-modified toluene diisocyanate, etc. can be mentioned. These can be used alone or in combination of two or more. Among them, trifunctional polyisocyanate-based compounds, i.e., toluene diisocyanate and their trimethylolpropane adducts and triphenylmethane isocyanate are particularly preferred.

[0049] As an index of the degree of crosslinking, the value of the gel fraction of the insoluble components after the above-mentioned adhesive layer is immersed in toluene for 24 hours is used. The above-mentioned gel fraction of the above-mentioned adhesive layer is not particularly limited and can be appropriately selected according to the purpose, preferably 10% by weight to 70% by weight, more preferably 25% by weight to 65% by weight, and further preferably 35% by weight to 60% by weight from the aspect of obtaining an adhesive layer with good cohesiveness and adhesion.

[0050] It should be noted that the gel fraction refers to the value measured by the following method. An adhesive composition containing the above-mentioned adhesive resin and the above-mentioned additives used as needed is applied on a release sheet so that the thickness after drying becomes 50 μm, dried at 100°C for 3 minutes, and aged at 40°C for 2 days. The obtained product is cut into 50 mm squares and used as a sample. Next, the weight (G1) of the above-mentioned sample before toluene immersion is measured in advance, and the toluene insoluble components of the sample after immersion in a toluene solution at 23°C for 24 hours are filtered through a 300-mesh metal mesh to separate them, and the weight (G2) of the residue after drying at 110°C for 1 hour is measured, and the gel fraction is calculated according to the following formula (4). It should be noted that the weight (G3) of the conductive particles in the sample is calculated based on the weight (G1) of the sample and the composition of the adhesive composition. Gel fraction (weight %) = (G2-G3) / (G1-G3)×100 Formula (4)

[0051] --Rubber-based adhesive resin-- The rubber-based binder resin is not particularly limited, and examples thereof include resins containing rubber materials commonly used as binder resins, such as synthetic rubber-based binder resins and natural rubber-based binder resins, and optionally used additives such as tackifier resins.

[0052] As the above-mentioned rubber material, for example, block copolymers of polyaromatic vinyl compounds and conjugated diene compounds can be cited; styrene resins such as styrene-isoprene copolymers, styrene-isoprene-styrene copolymers, styrene-butadiene-styrene copolymers, styrene-ethylene-butylene copolymers, and styrene-ethylene-propylene copolymers, etc. They can be used alone or in combination of two or more. Among them, the above-mentioned styrene resins are preferred, and using two or more of the above-mentioned styrene resins can give excellent adhesive properties and holding power to the above-mentioned adhesive sheet, so it is more preferred, and it is particularly preferred to use the above-mentioned styrene-isoprene copolymer and styrene-isoprene-styrene copolymer in combination.

[0053] The above-mentioned styrene resin may be, for example, a styrene resin having a single structure of a linear structure, a branched structure or a multi-branched structure, or a mixture of styrene resins of different structures. When a styrene resin rich in the above-mentioned linear structure is used for the above-mentioned adhesive layer, excellent bonding performance can be imparted to the above-mentioned adhesive sheet. On the other hand, although it is a branched structure or a multi-branched structure, a structure in which a styrene block is disposed at the molecular end can adopt a pseudo-crosslinked structure, which can impart excellent cohesive force, and thus can impart high holding power. Therefore, the above-mentioned styrene resin is preferably used in a mixture according to the required characteristics.

[0054] As the above-mentioned styrene resin, it is preferred to use a styrene resin having a structural unit represented by the following chemical formula (1) in an amount of 10% to 80% by weight, more preferably 12% to 60% by weight, further preferably 15% to 40% by weight, and particularly preferably 17% to 35% by weight, relative to the total weight of the styrene resin. Thus, excellent adhesiveness and heat resistance can be obtained.

[0055]

Chemical formula 1

[0056] When the styrene resin is used in combination with the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer, the content of the styrene-isoprene copolymer is preferably 0% to 80% by weight, more preferably 0% to 77% by weight, further preferably 0% to 75% by weight, and particularly preferably 0% to 70% by weight, relative to the total weight of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer. If the content of the styrene-isoprene copolymer is within the preferred range, the adhesive sheet can have both excellent adhesive performance and thermal durability.

[0057] In addition, as the above-mentioned styrene-isoprene copolymer, it is preferred to use a styrene-isoprene copolymer with a weight average molecular weight of 10,000 to 800,000 measured in terms of standard polystyrene by gel permeation chromatography (GPC), more preferably a styrene-isoprene copolymer with a weight average molecular weight of 30,000 to 500,000, and further preferably a styrene-isoprene copolymer with a weight average molecular weight of 50,000 to 300,000. By making the weight average molecular weight of the above-mentioned styrene-isoprene copolymer within the above-mentioned preferred range, the heat flowability and compatibility during solvent dilution can be ensured, so that the above-mentioned adhesive sheet with good workability in the manufacturing process and heat durability can be obtained, which is preferred.

[0058] Here, the weight average molecular weight of the styrene-isoprene copolymer measured by the GPC method is a standard polystyrene conversion value measured using a GPC apparatus (SC-8020, manufactured by Tosoh Corporation), and the measurement conditions are as follows. -Measurement conditions- Sample concentration: 0.5 wt% (tetrahydrofuran solution) Sample injection volume: 100μL ·Eluent: Tetrahydrofuran Flow rate: 1.0mL / min ·Measurement temperature: 40℃ Main column: TSKgel (registered trademark) GMHHR-H (20) 2 pieces Guard column: TSKgel HXL-H Detector: Differential refractometer · Standard polystyrene molecular weight: 10,000 to 20,000,000 (manufactured by Tosoh Corporation)

[0059] The method for producing the styrene-isoprene copolymer is not particularly limited and may be appropriately selected from conventionally known production methods. Examples thereof include a method of sequentially polymerizing a styrene block and an isoprene block by an anionic living polymerization method.

[0060] There are no particular restrictions on the method for producing the styrene-isoprene-styrene copolymer, and the method can be appropriately selected from conventionally known production methods. For example, there can be mentioned a method of sequentially polymerizing a styrene block and an isoprene block by an anionic living polymerization method, a method of producing a block copolymer having an activated living terminal and then reacting the block copolymer with a coupling agent to couple the block copolymer, and the like.

[0061] The method for producing the mixture of the above-mentioned styrene-isoprene copolymer and the above-mentioned styrene-isoprene-styrene copolymer is not particularly limited and can be appropriately selected from conventionally known production methods. For example, there can be mentioned a method of mixing the above-mentioned styrene-isoprene copolymer produced by the above-mentioned method with the above-mentioned styrene-isoprene-styrene copolymer.

[0062] In addition, as a method for producing a mixture of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer, the mixture may be produced simultaneously in one polymerization step. As a more specific embodiment, by anionic living polymerization, first, styrene monomer is polymerized in a polymerization solvent using an anionic polymerization initiator to form a polystyrene block having an activated active end. Second, isoprene is polymerized from the activated active end of the polystyrene block to obtain a styrene-isoprene diblock copolymer having an activated active end. Third, a portion of the above-mentioned styrene-isoprene diblock copolymer having an activated active end is reacted with a coupling agent to form a coupled styrene-isoprene-styrene block copolymer. Fourth, the remaining portion of the above-mentioned styrene-isoprene diblock copolymer having an activated active end is deactivated using a polymerization terminator to form a styrene-isoprene diblock copolymer.

[0063] The tackifier resin contained in the rubber-based adhesive resin is not particularly limited and can be appropriately selected depending on the purpose, but preferably a tackifier resin having a softening point of 80° C. or higher is used. This can provide the PSA sheet having excellent initial adhesiveness and heat durability.

[0064] As the above-mentioned tackifying resin, a tackifying resin that is solid at room temperature (23° C.) is preferred. Specific examples thereof include petroleum resins such as C5-based petroleum resins, C9-based petroleum resins, C5-based / C9-based petroleum resins, alicyclic petroleum resins, polymerized rosin-based resins, terpene-based resins, rosin-based resins, terpene-phenolic resins, styrene resins, coumarone-indene resins, xylene resins, phenolic resins, etc. These can be used alone or in combination of two or more. Among them, as the above-mentioned tackifying resin, it is preferred to use the above-mentioned C5-based petroleum resin and polymerized rosin-based resin in combination in order to achieve further excellent initial adhesion and thermal durability.

[0065] The petroleum resin is easily compatible with the structural unit represented by the chemical formula (1) constituting the styrene-based resin, and as a result, the initial adhesive force and thermal durability of the pressure-sensitive adhesive sheet can be further improved.

[0066] Examples of the C5 petroleum resin include Escorez 1202, Escorez 1304, and Escorez 1401 (all manufactured by ExxonMobil Corporation), Wingtack 95 (manufactured by Goodyear Tire and Rubber Company), Quintone K100, Quintone R100, and Quintone F100 (all manufactured by Nippon Zeon Co., Ltd.), Piccotac 95, and Piccopale 100 (manufactured by Rika Hercules Co., Ltd.), and the like.

[0067] Examples of the C9-based petroleum resins include Nippon Neopolymer L-90, Nippon Neopolymer 120, Nippon Neopolymer 130, Nippon Neopolymer 140, Nippon Neopolymer 150, Nippon Neopolymer 170S, Nippon Neopolymer 160, Nippon Neopolymer E-100, Nippon Neopolymer E-130, Nippon Neopolymer 130S, and Nippon Neopolymer S (all manufactured by JX Nippon Oil & Energy Co., Ltd.), and Petcol (registered trademark) (manufactured by Tosoh Corporation).

[0068] As the C5 / C9 petroleum resin, a copolymer of the C5 petroleum resin and the C9 petroleum resin can be used, for example, Escorez 2101 (manufactured by ExxonMobil Corporation), Quintone G115 (manufactured by Zeon Co., Ltd.), Hercotac 1149 (manufactured by Rika Hercules Co., Ltd.) and the like can be used.

[0069] The alicyclic petroleum resin can be obtained by hydrogenating the C9 petroleum resin, and examples thereof include Escorez 5300 (manufactured by ExxonMobil Corporation), Alcon P-100 (manufactured by Arakawa Chemical Industries, Ltd.), and Rigalite R101 (manufactured by Rika Hercules Co., Ltd.).

[0070] The amount of the tackifier resin used is not particularly limited and can be appropriately selected according to the purpose. It is preferably used in the range of 0 wt % to 100 wt %, more preferably in the range of 0 wt % to 70 wt %, further preferably in the range of 0 wt % to 50 wt %, and particularly preferably in the range of 0 wt % to 30 wt % relative to the total amount of the components constituting the rubber-based adhesive resin. By using the tackifier resin within the preferred range, it is easy to improve the interface adhesion between the adhesive layer and the substrate layer while taking into account the excellent elongation at break and thermal durability of the adhesive sheet.

[0071] The amount of the tackifier resin having a softening point of 80° C. or higher used is not particularly limited and can be appropriately selected according to the purpose. It is preferably used in the range of 3% by weight to 100% by weight, more preferably in the range of 5% by weight to 80% by weight, relative to the total amount of the styrene-based resin. In order to obtain the adhesive sheet having both further excellent adhesion and excellent thermal durability, it is particularly preferably used in the range of 5% by weight to 80% by weight.

[0072] In order to obtain adhesion and initial adhesion in a constant temperature environment, a tackifier resin having a softening point of -5°C or lower may be used in combination with the tackifier resin having a softening point of 80°C or higher.

[0073] The tackifier resin having a softening point of -5°C or lower is not particularly limited and can be appropriately selected from the known tackifier resins according to the purpose. It is preferred to use a tackifier resin that is liquid at room temperature.

[0074] Specific examples of the tackifying resin having a softening point of -5°C or less include process oil, polyester, liquid rubber such as polybutene, etc. These can be used alone or in combination of two or more. Among them, the tackifying resin having a softening point of -5°C or less using polybutene is preferred because it exhibits further excellent initial adhesion.

[0075] The tackifier resin having a softening point of -5°C or lower is preferably used in an amount within a range of 0% to 40% by weight, more preferably 0% to 30% by weight, based on the total amount of the tackifier resin.

[0076] In addition, the above-mentioned tackifying resin having a softening point below -5°C is preferably used in a range of 0 wt% to 40 wt% relative to the total amount of the above-mentioned styrene-based resin. Using it in a range of 0 wt% to 30 wt% can improve the initial bonding force and achieve good bonding, and can obtain sufficient thermal durability, so it is more preferred.

[0077] There is no particular restriction on the weight ratio of the tackifying resin having a softening point of 80°C or higher to the tackifying resin having a softening point of -5°C or lower, and it can be appropriately selected according to the purpose. The weight ratio of the tackifying resin having a softening point of 80°C or higher to the tackifying resin having a softening point of -5°C or lower, expressed as [weight of tackifying resin having a softening point of 80°C or higher / weight of tackifying resin having a softening point of -5°C or lower], is preferably used in the range of 5 to 50, and using it in the range of 10 to 30 can obtain the above-mentioned adhesive sheet having both excellent initial adhesion and excellent holding power, so it is more preferred.

[0078] The weight ratio of the styrene resin to the tackifying resin is not particularly limited and can be appropriately selected according to the purpose. The weight ratio of the styrene resin expressed as [styrene resin / tackifying resin] relative to the tackifying resin is preferably used in the range of 0.5 to 10.0. Using it in the range of 0.6 to 9.0 can improve the initial bonding force and obtain excellent thermal durability, so it is more preferred. In addition, the weight ratio [styrene resin / tackifying resin] is greater than 1, for example, when attached to the curved surface of the adherend, it can prevent the peeling (resistance to rebound) caused by the resilience of the adhesive sheet, so it is preferred.

[0079] -Other ingredients- As the above-mentioned other components in the above-mentioned adhesive layer, there is no particular limitation, and they can be appropriately selected within the range that does not damage the characteristics of the above-mentioned adhesive sheet, for example, polymer components other than the above-mentioned adhesive resin, crosslinking agents, anti-aging agents, ultraviolet absorbers, fillers, inhibitors, surface regulators, antistatic agents, defoamers, viscosity modifiers, light stabilizers, weather stabilizers, heat stabilizers, antioxidants, leveling agents, organic pigments, inorganic pigments, pigment dispersants, plasticizers, softeners, flame retardants, metal deactivators, silica beads, organic beads and other additives; inorganic fillers such as silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, antimony pentoxide, etc. They can be used alone or in combination of two or more. The content of the other components in the adhesive layer may be appropriately selected within a range that does not impair the properties of the adhesive sheet.

[0080] The adhesive layer is not particularly limited as long as it is disposed on the surface of the substrate layer, and can be appropriately selected depending on the intended use, etc. It may be disposed on only one side of the substrate layer or on both sides, preferably on both sides.

[0081] <<Stress when the adhesive layer is elongated by 25%>> The stress of the adhesive layer at 25% elongation is not particularly limited and can be appropriately selected according to the purpose, preferably 0.04MPa to 0.4MPa, more preferably 0.05MPa to 0.1MPa. If the stress of the adhesive layer at 25% elongation is within the preferred range, a bonding strength suitable for the adhesive sheet can be obtained, and it can be relatively easy to peel off even when the adhesive sheet is elongated and peeled off. On the other hand, if the stress of the adhesive layer at 25% elongation is less than 0.04MPa, when the adhesive sheet generates a load in the shear direction while fixing the hard adherends to each other, the adhesive sheet is sometimes peeled off. If it exceeds 0.4MPa, when peeling the adhesive sheet, the force required to stretch the adhesive sheet sometimes becomes too large. The stress of the adhesive layer when it is elongated by 25% refers to the stress value measured when the adhesive layer is punched into a dumbbell shape with a marking line length of 20 mm and a width of 10 mm, and stretched in the longitudinal direction at a stretching speed of 300 mm / min under the conditions of a measuring atmosphere of 23°C and 50% RH using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) and elongated by 25%.

[0082] <<Breaking stress of adhesive layer>> As the fracture stress of the above-mentioned adhesive layer, there is no particular limitation, and it can be appropriately selected according to the purpose, preferably 0.5MPa~2.1MPa, and more preferably 1.0MPa~2.1MPa. If the fracture stress of the above-mentioned adhesive layer is within the above-mentioned preferred range, the adhesive sheet can also be suppressed from being torn when the above-mentioned adhesive sheet is stretched and peeled off, and the load used to make the adhesive sheet elongated will not be excessive, so the re-peeling operation based on peeling becomes easy. On the other hand, if the fracture stress of the above-mentioned adhesive layer is less than 0.5MPa, the adhesive sheet is torn when the above-mentioned adhesive sheet is stretched and peeled off. If it exceeds 2.1MPa, when the above-mentioned adhesive sheet is stretched and peeled off again, it is sometimes impossible to fully stretch and cannot be peeled off again. It should be noted that the force required when the above-mentioned adhesive sheet is stretched and deformed also depends on the thickness of the adhesive sheet. For example, when the adhesive sheet with a thick thickness and high fracture stress is stretched and peeled off again, it is sometimes impossible to fully stretch and cannot be peeled off again. The breaking stress of the adhesive layer refers to the stress value measured when the adhesive layer is punched into a dumbbell shape with a marking line length of 20 mm and a width of 10 mm, and stretched in the longitudinal direction at a stretching speed of 300 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH.

[0083] <<Elongation at break of adhesive layer>> The elongation at break of the adhesive layer is not particularly limited and can be appropriately selected according to the purpose, preferably 450% to 1300%, more preferably 500% to 1200%, and further preferably 600% to 1100%. By making the elongation at break of the adhesive layer within the above preferred range, both suitable adhesion and removability can be taken into account. The elongation at break of the adhesive layer is the tensile elongation obtained by punching the adhesive layer into a dumbbell shape with a marking length of 20 mm and a width of 10 mm, stretching the adhesive layer in the longitudinal direction at a stretching speed of 300 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH, and measuring the tensile elongation at break.

[0084] <<Average thickness of adhesive layer>> The average thickness of the adhesive layer is not particularly limited and can be appropriately selected according to the purpose. It is preferably 5 μm to 150 μm, more preferably 20 μm to 120 μm, further preferably 40 μm to 110 μm, and particularly preferably 50 μm to 100 μm. The above-mentioned "average thickness of the adhesive layer" refers to the average thickness of the adhesive layer on one side of the adhesive sheet. In the case where the adhesive layer is provided on both sides of the adhesive sheet, the average thickness of the adhesive layer on one side and the average thickness of the adhesive layer on the other side may be the same thickness or different thicknesses, preferably the same thickness. It should be noted that in the present specification, the "average thickness of the adhesive layer" refers to the average value of the thickness of 25 positions in total obtained by cutting the above-mentioned adhesive sheet in the width direction at 5 positions at intervals of 100 mm in the length direction, and measuring the total thickness of the above-mentioned adhesive layer at 5 positions in the width direction at intervals of 100 mm in each of the above-mentioned cut surfaces using a TH-104 paper / film thickness measuring machine (manufactured by TESTER SANGYO Co., Ltd.).

[0085] <<Method for forming adhesive layer>> There is no particular limitation on the method for forming the adhesive layer, and the method can be appropriately selected from known methods according to the purpose, and examples thereof include a method of forming the adhesive layer on at least one side of the substrate layer by a hot pressing method, a casting method based on extrusion molding, a uniaxial stretching method, a sequential secondary stretching method, a simultaneous biaxial stretching method, an inflation method, a tube method, a calendering method, a solution method, etc. Among them, a casting method based on extrusion molding and a solution method are preferred.

[0086] Examples of the solution method include a method of directly applying a solution containing the pressure-sensitive adhesive composition onto the substrate layer using a roll coater or the like, and a method of forming the pressure-sensitive adhesive layer on a release sheet and then peeling the sheet off.

[0087] The release sheet is not particularly limited and can be appropriately selected according to the purpose, for example, kraft paper, glassine paper, high-grade paper, etc.; resin films such as polyethylene, polypropylene (biaxially stretched polypropylene (OPP), uniaxially stretched polypropylene (CPP)), polyethylene terephthalate (PET), etc.; laminated paper obtained by laminating the above paper with a resin film, paper obtained by caulking the above paper with clay, polyvinyl alcohol, etc., one or both sides of which are subjected to a release treatment of silicone resin, etc., etc. These can be used alone or in combination of two or more.

[0088] <Base material layer> The substrate layer is not particularly limited and can be appropriately selected from known materials that can be used for pressure-sensitive adhesive sheets within a range that does not impair the properties of the pressure-sensitive adhesive sheet. The substrate layer preferably includes the following substrate materials and may include other components as necessary. The substrate layer may have a single-layer structure or a multi-layer structure of two, three or more layers.

[0089] <<Material for base material>> As the material for the substrate, for example, styrene resins such as styrene-isoprene copolymer, styrene-isoprene-styrene copolymer, styrene-butadiene-styrene copolymer, styrene-ethylene-butylene copolymer, and styrene-ethylene-propylene copolymer can be cited; polyurethane resins such as ester polyurethane and ether polyurethane; polyolefin resins such as polyethylene and polypropylene; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polystyrene; polycarbonate; polymethylpentene; polysulfone; polyetheretherketone; polyethersulfone; polyetherimide; polyimide film; fluororesin; nylon; acrylic resin, etc. These can be used alone or in combination of two or more, preferably in combination of two or more. Among them, the styrene resin and the polyurethane resin are preferred because they can easily provide suitable elongation at break and stress at break. The styrene resin is more preferred, and a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer are particularly preferably used in combination.

[0090] -Styrene resin- The above-mentioned styrene resin is a resin showing thermoplasticity, so it is excellent in formability such as extrusion molding and injection molding, and it is easy to shape the above-mentioned base layer. In addition, the above-mentioned styrene resin is easy to obtain particularly excellent elongation at break in the resin group generally referred to as thermoplastic resins, and can be preferably used as the base material of the above-mentioned adhesive sheet.

[0091] Therefore, in the above-mentioned substrate material, the proportion of the above-mentioned styrene resin relative to the total resin components is preferably 50% to 100%, more preferably 60% to 100%, further preferably 65% ​​to 100%, and particularly preferably 70% to 100%. By making the proportion of the above-mentioned styrene resin within the above-mentioned preferred range, a substrate layer having excellent elongation at break and breaking stress can be obtained.

[0092] The above-mentioned styrene resin can be, for example, a styrene resin of a single structure of a linear structure, a branched structure or a multi-branched structure, or a mixture of styrene resins of different structures. The above-mentioned styrene resin rich in linear structure can give the above-mentioned substrate layer an excellent elongation at break. On the other hand, in the case of a branched structure or a multi-branched structure and a styrene block at the molecular end, a pseudo-crosslinked structure can be adopted, which can give excellent cohesive force. Therefore, the above-mentioned styrene resin is preferably used in a mixture according to the required mechanical properties.

[0093] As the above-mentioned styrene resin, it is preferred to use a styrene resin having the structural unit represented by the above-mentioned chemical formula (1) in a range of 13% to 60% by weight, more preferably 15% to 50% by weight, further preferably 15% to 45% by weight, and particularly preferably 15% to 35% by weight. By making the ratio of the structural unit represented by the following chemical formula (1) to the total weight of the above-mentioned styrene resin within the above-mentioned preferred range, it is easy to obtain the elongation at break and the stress at break within a suitable range.

[0094] When the styrene-based resin is used in combination with the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer, the content of the styrene-isoprene copolymer is preferably 0% to 80% by weight, more preferably 0% to 70% by weight, further preferably 0% to 50% by weight, and particularly preferably 0% to 30% by weight, relative to the total weight of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer. If the content of the styrene-isoprene copolymer is within the preferred range, thermal durability can be achieved while maintaining excellent elongation at break and stress at break.

[0095] In addition, as the styrene-isoprene copolymer, it is preferred to use a styrene-isoprene copolymer having a weight average molecular weight of 10,000 to 800,000 as measured by gel permeation chromatography (GPC) in terms of standard polystyrene, more preferably 30,000 to 500,000, and even more preferably 50,000 to 300,000. By making the weight average molecular weight of the styrene-isoprene copolymer within the preferred range, the heat flowability and compatibility during solvent dilution can be ensured, so that the substrate layer having good workability in the manufacturing process and heat durability can be obtained, which is preferred. The measurement of the weight average molecular weight of the styrene-isoprene copolymer by the GPC method is the same as the method described in the above-mentioned section "-Rubber-based Binder Resin-".

[0096] There are no particular restrictions on the method for producing the above-mentioned styrene-isoprene copolymer, the above-mentioned styrene-isoprene-styrene copolymer, and the mixture of the above-mentioned styrene-isoprene copolymer and the above-mentioned styrene-isoprene-styrene copolymer, and they can be appropriately selected from conventionally known production methods, for example, the same method as described in the above-mentioned item "-Rubber-based binder resin-" can be cited.

[0097] -Polyurethane resin- The polyurethane resin is not particularly limited and can be appropriately selected according to the purpose. A polyurethane resin having a softening point of 40° C. or higher is preferred, and a polyurethane resin having a softening point of 50° C. or higher is more preferred. The upper limit of the softening point is preferably 100° C. or lower. The softening point refers to a value measured according to JIS K 2207 (dry bulb method) (hereinafter, the softening point is the same).

[0098] As the polyurethane resin, a reaction product of a polyol (b1-1) and a polyisocyanate (b1-2) can be preferably used.

[0099] As the above-mentioned polyol (b1-1), there is no particular limitation, and it can be appropriately selected according to the purpose, for example, polyester polyol, polyether polyol, polycarbonate polyol, acrylic polyol, etc. can be cited. They can be used alone or in combination of two or more. Among them, as the above-mentioned polyol (b1-1), the mechanical properties of the above-mentioned substrate layer can be obtained, so polyester polyol and polyether polyol are preferred. In the above-mentioned substrate layer, when heat resistance is required, polyester polyol is preferably used, and when water resistance and biodegradability resistance are required, polyether polyol is preferably used.

[0100] Examples of the polyester polyol include polyesters obtained by esterification reaction of a low molecular weight polyol and a polycarboxylic acid, polyesters obtained by ring-opening polymerization of a cyclic ester compound such as ε-caprolactone, and copolymerized polyesters thereof.

[0101] Examples of the low molecular weight polyol that can be used in the production of the polyester polyol include aliphatic alkylene glycols such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, neopentyl glycol, and 1,3-butanediol, and cyclohexanedimethanol having a weight average molecular weight of about 50 to 300.

[0102] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and dodecanedicarboxylic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and naphthalenedicarboxylic acid; and anhydrides or esters thereof.

[0103] Examples of the polyether polyol include polyether polyols obtained by addition-polymerizing alkylene oxides using one or more compounds having two or more active hydrogen atoms as initiators.

[0104] As the polycarbonate polyol, for example, a polycarbonate polyol obtained by reacting a carbonate and / or phosgene with a low molecular weight polyol described below can be used.

[0105] Examples of the carbonate ester include methyl carbonate, dimethyl carbonate, ethyl carbonate, diethyl carbonate, cyclic carbonate, and diphenyl carbonate.

[0106] Examples of the low molecular weight polyol that can be used in the production of the polycarbonate polyol and that can react with the carbonate and / or phosgene include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, dipropylene glycol, tripropylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,5-pentanediol, 1,5-hexanediol, 1,6-hexanediol, 2,5-hexanediol, 1,7- Heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol, 2-methyl-1,8-octanediol, 1,4-cyclohexanedimethanol, hydroquinone, resorcinol, bisphenol A, bisphenol F, 4,4'-biphenol, etc.

[0107] As the above-mentioned polyisocyanate (b1-2), there is no particular limitation and it can be appropriately selected according to the purpose, for example, alicyclic polyisocyanate, aliphatic polyisocyanate, aromatic polyisocyanate etc. can be used, and alicyclic polyisocyanate etc. can be mentioned. They can be used alone or in combination of two or more.

[0108] Examples of the alicyclic polyisocyanate include isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 4,4'-dicyclohexylmethane diisocyanate, 2,4-methylcyclohexane diisocyanate, 2,6-methylcyclohexane diisocyanate, cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexylene-1,2-dicarboxylate, 2,5-norbornane diisocyanate, 2,6-norbornane diisocyanate, dimer acid diisocyanate, and bicycloheptane triisocyanate. These may be used alone or in combination of two or more.

[0109] There is no particular limitation on the method for preparing the polyurethane resin (b1) by reacting the polyol (b1-1) with the polyisocyanate (b1-2). The method can be appropriately selected from conventionally known production methods. For example, the following method can be cited, wherein the polyol (b1-1) introduced into a reaction container is heated under normal pressure or reduced pressure to remove moisture, and then the polyisocyanate (b1-2) is supplied all at once or in batches to react.

[0110] The reaction of the above-mentioned polyol (b1-1) and the above-mentioned polyisocyanate (b1-2) is preferably carried out when the equivalent ratio of the isocyanate group (NCO) possessed by the above-mentioned polyisocyanate (b1-2) to the hydroxyl group (OH) possessed by the above-mentioned polyol (b1-1) (NCO / OH equivalent ratio) is in the range of 1.0 to 20.0, more preferably in the range of 1.1 to 13.0, further preferably in the range of 1.2 to 5.0, and particularly preferably in the range of 1.5 to 3.0.

[0111] The reaction conditions of the polyol (b1-1) and the polyisocyanate (b1-2) are not particularly limited and can be appropriately selected in consideration of various conditions such as safety, quality, and cost. The reaction temperature is preferably 70° C. to 120° C., and the reaction time is preferably 30 minutes to 5 hours.

[0112] When the polyol (b1-1) and the polyisocyanate (b1-2) are reacted, a catalyst such as a tertiary amine catalyst or an organic metal catalyst may be used as necessary.

[0113] In addition, the above reaction may be carried out in the absence of a solvent or in the presence of an organic solvent. The organic solvent is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include ester solvents such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate; ketone solvents such as acetone, methyl ethyl ketone, methyl butyl ketone, and cyclohexanone; ether ester solvents such as methyl cellosolve acetate and butyl cellosolve acetate; aromatic hydrocarbon solvents such as toluene and xylene; amide solvents such as dimethylformamide and dimethylacetamide, etc. These solvents can be used alone or in combination of two or more. The organic solvent can be removed by an appropriate method such as heating under reduced pressure, drying under normal pressure, etc. during the production of the polyurethane resin (b1) or after the production of the polyurethane (b1).

[0114] -Other ingredients- As the above-mentioned other components in the above-mentioned substrate layer, there is no particular limitation, and they can be appropriately selected within the range that does not damage the characteristics of the above-mentioned adhesive sheet, for example, tackifying resins can be cited; polymer components other than the above-mentioned substrate materials; crosslinking agents, anti-aging agents, ultraviolet absorbers, fillers, inhibitors, surface regulators, antistatic agents, defoamers, viscosity modifiers, light stabilizers, weather stabilizers, heat stabilizers, antioxidants, leveling agents, organic pigments, inorganic pigments, pigment dispersants, silica beads, organic beads and other additives; inorganic fillers such as silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, antimony pentoxide, etc. They can be used alone or in combination of two or more. The content of the other components in the base layer may be appropriately selected within a range that does not impair the properties of the pressure-sensitive adhesive sheet.

[0115] The tackifier resin is used to improve the adhesion between the adhesive layer and the base layer in the adhesive sheet and to improve heat resistance.

[0116] The tackifier resin is not particularly limited and can be appropriately selected according to the purpose. A tackifier resin having a softening point of 80° C. or higher is preferred, 90° C. or higher is more preferred, 100° C. or higher is further preferred, and 110° C. or higher is particularly preferred.

[0117] As the tackifier resin, for example, the tackifier resins described in the above-mentioned section "-Rubber-based binder resin-" can be used, and preferred aspects and the like are also the same.

[0118] As the above-mentioned antioxidant, there is no particular limitation, and it can be appropriately selected from known antioxidants according to the purpose, for example, phenolic antioxidants, phosphorus antioxidants (sometimes also referred to as "processing stabilizers"), amine antioxidants, imidazole antioxidants, etc. can be cited. They can be used alone or in combination of two or more. Among them, the above-mentioned phenolic antioxidants and phosphorus antioxidants are preferred, and their combination can effectively improve the heat resistance stability of the above-mentioned substrate material, and as a result, it is possible to obtain an adhesive sheet that maintains good initial adhesion and has further excellent thermal durability, so it is preferred. It should be noted that the above-mentioned phosphorus antioxidant sometimes changes color (yellowing) slightly over time under high temperature conditions, so its usage is preferably appropriately set in consideration of the above-mentioned initial adhesion, thermal durability and the balance of preventing discoloration.

[0119] As the above-mentioned phenolic antioxidant, a phenolic compound generally having a sterically hindered group can be used, and representative ones are monophenol type, bisphenol type, and polyphenol type. As specific examples, 2,6-di-tert-butyl-4-methylphenol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-thiobis(6-tert-butyl-3-methylphenol), 4,4'-butylenebis(3-methyl-6-tert-butylphenol), tetrakis-[methylene-3-(3'5'-di-tert-butyl-4-hydroxyphenyl) propionate]methane, n-octadecyl-3-(4'-hydroxy-3'5'-di-tert-butylphenyl) propionate, etc. can be cited. One of them can be used alone, or two or more of them can be used in combination.

[0120] The amount of the phenolic antioxidant used is not particularly limited and can be appropriately selected according to the purpose. It is preferably used in the range of 0.1 to 5 parts by weight relative to 100 parts by weight of the substrate material. Using it in the range of 0.5 to 3 parts by weight can effectively improve the heat resistance stability of the substrate material. As a result, an adhesive sheet that maintains good initial adhesion and has further excellent thermal durability can be obtained.

[0121] <<Stress when the base material layer is elongated by 25%>> The stress when the substrate layer is elongated by 25% is not particularly limited and can be appropriately selected according to the purpose. It is preferably 0.2MPa to 10.0MPa, more preferably 0.2MPa to 5.0MPa, further preferably 0.2MPa to 3.0MPa, and particularly preferably 0.2MPa to 2.0MPa. If the stress when the substrate layer is elongated by 25% is within the preferred range, a bonding strength suitable for the adhesive sheet can be obtained, and it can be relatively easy to peel off even when the adhesive sheet is elongated and peeled off. On the other hand, if the stress when the substrate layer is elongated by 25% is less than 0.2MPa, when the adhesive sheet generates a load in the shear direction while fixing the hard adherends to each other, the adhesive sheet is sometimes peeled off. If it exceeds 10.0MPa, when the adhesive sheet is peeled off, the force required to stretch the adhesive sheet sometimes becomes too large. The stress at which the substrate layer is elongated by 25% refers to the stress value obtained by punching the substrate layer into a dumbbell shape with a marking length of 20 mm and a width of 6 mm, and stretching it in the longitudinal direction at a stretching speed of 500 mm / min under the conditions of a measuring atmosphere of 23°C and 50% RH using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.).

[0122] <<Breaking stress of base material layer>> As the fracture stress of the above-mentioned substrate layer, there is no particular limitation, and it can be appropriately selected according to the purpose, preferably 1.5MPa~100.0MPa, more preferably 7.0MPa~50.0MPa, further preferably 7.0MPa~40.0MPa, and particularly preferably 8.0MPa~35.0MPa. If the fracture stress of the above-mentioned substrate layer is within the above-mentioned preferred range, the adhesive sheet can also be suppressed from being torn when the above-mentioned adhesive sheet is stretched and peeled off, and the load for stretching the adhesive sheet will not be excessive, so the re-peeling operation based on peeling becomes easy. On the other hand, if the fracture stress of the above-mentioned substrate layer is less than 1.5MPa, when the above-mentioned adhesive sheet is stretched and peeled off, the adhesive sheet is sometimes torn, and if it exceeds 100.0MPa, when the above-mentioned adhesive sheet is stretched and peeled off, it is sometimes not fully stretched and cannot be peeled off. The force required to stretch and deform the PSA sheet also depends on the thickness of the PSA sheet. For example, when a thick PSA sheet with a high breaking stress is stretched and then peeled off, it may not be stretched sufficiently and cannot be peeled off. The breaking stress of the substrate layer refers to the stress value measured when the substrate layer is punched into a dumbbell shape with a marking line length of 20 mm and a width of 6 mm, and stretched in the longitudinal direction at a stretching speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH.

[0123] <<Elongation at break of base material layer>> The elongation at break of the substrate layer is not particularly limited and can be appropriately selected according to the purpose, preferably 200% to 1300%, more preferably 400% to 1300%, and further preferably 700% to 1300%. If the elongation at break of the substrate layer is 200% or more, even if the adhesive sheet is firmly bonded to the adherend, when the adhesive sheet is peeled off again, the stress for stretching in the horizontal direction to the vertical direction relative to the attached surface of the adherend will not become too large, and the adhesive sheet will not be overstretched during peeling, and can be easily peeled off. In addition, if the elongation at break is less than 1300%, when the adhesive sheet is peeled off again, the stretching distance in the horizontal direction to the vertical direction relative to the attached surface of the adherend will not become too long, and the operation can be performed in a small space. On the other hand, if the elongation at break is less than 200%, when the adhesive sheet is peeled off again, it may break and cannot be peeled off when it is stretched and peeled off in the horizontal direction to the vertical direction relative to the attachment surface of the adherend. If it exceeds 1300%, when the adhesive sheet is peeled off again, the stretching distance in the horizontal direction to the vertical direction relative to the attachment surface of the adherend becomes too long, so the workability may deteriorate. The elongation at break of the substrate layer refers to the tensile elongation measured when the substrate layer is punched into a dumbbell shape with a marking line length of 20 mm and a width of 6 mm, and stretched in the longitudinal direction at a stretching speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH.

[0124] <<Average thickness of base material layer>> The average thickness of the substrate layer is not particularly limited and can be appropriately selected according to the purpose of use, and is preferably 10 μm to 500 μm, more preferably 10 μm to 300 μm, further preferably 20 μm to 200 μm, and particularly preferably 20 μm to 100 μm. If the average thickness of the substrate layer is within the preferred range, the adhesive sheet can easily follow the strain of the adherend and easily obtain high bonding strength. When the adhesive sheet having the substrate layer is stretched in the horizontal direction to the vertical direction relative to the attachment surface of the adherend and then peeled off, the required stress will not become too large, so it is preferred. It should be noted that in this specification, the "average thickness of the substrate layer" refers to the average value of the thickness of 25 positions in total obtained by cutting the above-mentioned substrate layer at 5 positions in a direction perpendicular to the length direction (sometimes also referred to as the "width direction") at intervals of 100 mm in the length direction, and measuring the thickness at 5 positions in the width direction at intervals of 100 mm in each of the above-mentioned cut surfaces using a TH-104 paper / film thickness measuring machine (manufactured by TESTER SANGYO Co., Ltd.).

[0125] <<Average thickness of adhesive layer / Average thickness of base material layer>> As the ratio of the thickness of the above-mentioned adhesive layer to the above-mentioned substrate layer, there is no particular limitation and it can be appropriately selected according to the purpose. The ratio of the average thickness of the above-mentioned adhesive layer relative to the average thickness of the above-mentioned substrate layer represented by [average thickness of the adhesive layer / average thickness of the substrate layer] is preferably 1 / 5 to 5 / 1, more preferably 1 / 3 to 3 / 1, and further preferably 1 / 1 to 2 / 1. If the ratio of the average thickness of the above-mentioned adhesive layer to the average thickness of the above-mentioned substrate layer is within the above-mentioned preferred range, the excellent adhesion and re-peelability of the above-mentioned adhesive sheet can be obtained. On the other hand, if the above-mentioned ratio is greater than 5 / 1, it is possible that only the above-mentioned adhesive layer remains on the adherend in the re-peeling process of the above-mentioned adhesive sheet. In addition, if the above-mentioned ratio is less than 1 / 5, when the surface of the adherend is a concave-convex shape, the adhesive layer cannot follow, and the bonding strength may be significantly reduced.

[0126] <<Method for forming base material layer>> There is no particular limitation on the method for forming the substrate layer. It can be appropriately selected from known methods according to the mechanical strength required for the adhesive sheet, and examples thereof include hot pressing, casting based on extrusion molding, uniaxial stretching, sequential secondary stretching, simultaneous biaxial stretching, inflation, tube method, calendering, solution method, etc. Among them, one kind can be used alone, or two or more kinds can be used in combination. Among them, casting based on extrusion molding, inflation, tube method, calendering, and solution method give appropriate softness and ductility to the substrate layer, so it is preferred.

[0127] In addition, in order to further improve the adhesion with the above-mentioned adhesive layer, the above-mentioned base material layer may be subjected to a surface treatment. The surface treatment method is not particularly limited and can be appropriately selected from known methods within the range that does not impair the properties of the adhesive sheet. Examples thereof include sandblasting, surface grinding and friction, corona discharge treatment, chromic acid treatment, flame treatment, hot air treatment, ozone treatment, ultraviolet irradiation treatment, oxidation treatment, and the like.

[0128] <Other floors> The other layers in the pressure-sensitive adhesive sheet are not particularly limited and may be appropriately selected depending on the intended purpose. Examples thereof include a primer layer, an antistatic layer, a non-combustible layer, a decorative layer, a conductive layer, a thermal conductive layer, and a release layer.

[0129] The pressure-sensitive adhesive sheet having at least the pressure-sensitive adhesive layer and the base layer and, if necessary, the other layers described above preferably has the following properties.

[0130] <Hardness of adhesive sheet (Shore A hardness)> The hardness (Shore A hardness) of the adhesive sheet is not particularly limited and can be appropriately selected according to the purpose, preferably 10 to 90, more preferably 20 to 85, and further preferably 64 to 85. If the Shore A hardness of the adhesive sheet is within the preferred range, the re-peeling operation of the adhesive sheet based on peeling becomes easy. On the other hand, if the Shore A hardness is less than 10, when the adhesive sheet is stretched and peeled, the adhesive sheet is sometimes torn, and if it exceeds 90, when the adhesive sheet is stretched and peeled again, the stress used for stretching sometimes becomes too high and cannot be peeled again. The Shore A hardness of the PSA sheet is a value measured using a durometer (spring type rubber durometer) (model: GS-719G, manufactured by TECLOCK CO., LTD.) in accordance with JIS K 6253.

[0131] <Stress when the adhesive sheet is elongated by 25%> The stress when the above-mentioned adhesive sheet is elongated by 25% is 0.15Mpa to 82Mpa, preferably 0.15Mpa to 10Mpa, more preferably 0.15Mpa to 5Mpa, and further preferably 0.15Mpa to 2Mpa. If the stress when the above-mentioned adhesive sheet is elongated by 25% is 0.15Mpa to 82Mpa, a bonding strength suitable for the above-mentioned adhesive sheet can be obtained, and it can be relatively easy to peel off even when the elongation is peeled off. On the other hand, if the stress when the above-mentioned adhesive sheet is elongated by 25% is less than 0.15Mpa, the above-mentioned adhesive sheet will be peeled off when the load is generated in the shear direction while the hard adherends are fixed to each other. In addition, if the stress when the above-mentioned adhesive sheet is elongated by 25% exceeds 82Mpa, when the above-mentioned adhesive sheet is peeled off, the force required to elongate the adhesive sheet becomes too large. The stress of the adhesive sheet at an elongation of 25% refers to the stress value measured when the adhesive sheet is punched into a dumbbell shape with a marking line length of 20 mm and a width of 6 mm, and stretched in the longitudinal direction at a stretching speed of 500 mm / min under the conditions of a measuring atmosphere of 23°C and 50% RH using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) and elongated by 25%.

[0132] <Breaking stress of adhesive sheet> As the breaking stress of the above-mentioned adhesive sheet, there is no particular limitation, and it can be appropriately selected according to the purpose, preferably 1.5MPa~100.0MPa, more preferably 5.0MPa~50.0MPa, further preferably 5.0MPa~40.0MPa, and particularly preferably 5.0MPa~35.0MPa. If the breaking stress of the above-mentioned adhesive sheet is within the above-mentioned preferred range, the adhesive sheet can also be suppressed from being torn when the above-mentioned adhesive sheet is stretched and peeled off, and the load for stretching the adhesive sheet will not be excessive, so the re-peeling operation based on peeling becomes easy. On the other hand, if the breaking stress of the above-mentioned adhesive sheet is less than 1.5MPa, when the above-mentioned adhesive sheet is stretched and peeled off, the adhesive sheet is sometimes torn, and if it exceeds 100.0MPa, when the above-mentioned adhesive sheet is stretched and peeled off, it is sometimes not possible to fully stretch and cannot be peeled off. The force required to stretch and deform the PSA sheet also depends on the thickness of the PSA sheet. For example, when a thick PSA sheet with a high breaking stress is stretched and peeled off, it may not be stretched sufficiently and cannot be peeled off. The breaking stress of the above-mentioned adhesive sheet refers to the stress value measured when the above-mentioned adhesive sheet is punched into a dumbbell shape with a marking line length of 20 mm and a width of 6 mm, and stretched in the longitudinal direction at a stretching speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH, and the sheet is stretched.

[0133] <Elongation at break of adhesive sheet> There is no particular limitation on the elongation at break of the adhesive sheet, which can be appropriately selected according to the purpose, preferably 500% to 2000%, more preferably 600% to 1800%, and further preferably 800% to 1800%. If the elongation at break of the adhesive sheet is 500% or more, even if the adhesive sheet is firmly bonded to the adherend, when the adhesive sheet is peeled off again, the stress for stretching in the horizontal direction to the vertical direction relative to the attached surface of the adherend will not become too large, and when peeling off, the adhesive sheet will not be overstretched, and can be easily peeled off. In addition, if the elongation at break is less than 2000%, when the adhesive sheet is peeled off again, the stretching distance in the horizontal direction to the vertical direction relative to the attached surface of the adherend will not become too long, and the operation can be performed in a small space. On the other hand, if the elongation at break is less than 500%, when the adhesive sheet is peeled off again, it may be impossible to peel off due to breakage when it is stretched and peeled off in the horizontal to vertical directions relative to the attachment surface of the adherend. If it exceeds 1300%, when the adhesive sheet is peeled off again, the stretching distance in the horizontal to vertical directions relative to the attachment surface of the adherend will not become too long, so the workability may sometimes deteriorate. The elongation at break of the adhesive sheet is the tensile elongation obtained by punching the adhesive sheet into a dumbbell shape with a marking length of 20 mm and a width of 6 mm, stretching the sheet in the longitudinal direction at a stretching speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH, and measuring the tensile elongation at break.

[0134] <Removability of PSA Sheet (Perpendicular Tensile Peel)> The above-mentioned adhesive sheet can be easily stretched and peeled off even if the stretching direction is perpendicular to the attached surface of the adherend (90° direction). In this specification, the sticking property of the above-mentioned adhesive sheet when stretched and peeled in the perpendicular direction relative to the attached surface of the adherend is referred to as "re-peelability (vertical stretch peeling)". The above-mentioned re-peelability (vertical stretch peeling) can be confirmed, for example, by the method described in "Evaluation of re-peelability (vertical stretch peeling)" in the later-mentioned embodiments. In the evaluation of the above-mentioned re-peelability (vertical stretch peeling), the above-mentioned adhesive sheet is not easy to be torn, and the adhesive sheet with less adhesive composition residue in the adherend after the above-mentioned adhesive sheet is peeled off is an adhesive sheet with excellent re-peelability (vertical stretch peeling), and the above-mentioned adhesive sheet is not torn, and the adhesive sheet with no adhesive composition residue in the adherend after the above-mentioned adhesive sheet is peeled off is an adhesive sheet with even better re-peelability (vertical stretch peeling).

[0135] <Impact resistance of adhesive sheet> The above-mentioned adhesive sheet also has excellent impact resistance. The above-mentioned impact resistance can be confirmed, for example, by the method described in "Evaluation of Impact Resistance" in the examples described later. In the above-mentioned impact resistance evaluation, the height of the impact core that causes peeling or damage to the adhesive sheet can be appropriately selected within the range that does not impair the effect of the present invention, preferably 30 cm or more, more preferably 40 cm or more, further preferably 50 cm or more, and particularly preferably 60 cm or more. If the above-mentioned height is less than 30 cm, sufficient impact resistance cannot be obtained.

[0136] <180° Peel Adhesion Strength of PSA Sheet> The 180° peeling strength of the adhesive sheet is not particularly limited and can be appropriately selected according to the purpose, preferably 3N / 20mm to 35N / 20mm, more preferably 4N / 20mm to 30N / 20mm, and further preferably 5N / 20mm to 25N / 20mm. If the 180° peeling strength is within the preferred range, it will not cause peeling or displacement from the adherend and has a moderate adhesive strength, and when the adhesive sheet is stretched in the horizontal direction to the vertical direction relative to the attachment surface of the adherend and then peeled off, it can be easily peeled off. The 180° peel strength of the pressure-sensitive adhesive sheet is a value measured in accordance with JIS Z 0237.

[0137] <Shear Adhesion Strength of PSA Sheet> The adhesive sheet is not easily peeled off even when a load is applied to the adhesive sheet in a shear direction, and has excellent shear adhesion. The shear direction is not particularly limited as long as it is a direction perpendicular to the thickness direction of the adhesive sheet. The shear adhesive strength of the pressure-sensitive adhesive sheet can be appropriately selected within a range that does not impair the effects of the present invention, and is preferably 100 N / 4 cm 2 More than, more preferably 120N / 4cm 2 More than, more preferably 150N / 4cm 2 Above, particularly preferably 200N / 4cm 2 When the shear adhesive strength is within the preferred range, it is possible to suppress displacement when stress in a shear direction is applied to an adherend fixed by the pressure-sensitive adhesive sheet. The shear adhesive strength of the pressure-sensitive adhesive sheet can be confirmed, for example, by the method described in "Evaluation of Shear Adhesive Strength" in Examples described later.

[0138] <Separation Adhesion Strength of Adhesive Sheet> The adhesive sheet is not easily peeled off even when a load is applied in the tearing direction (sometimes also referred to as the "thickness direction") of the adhesive sheet, and has excellent tearing adhesion. The tearing adhesion of the adhesive sheet can be appropriately selected within a range that does not impair the effect of the present invention, and is preferably 80N / 4cm 2 More than, more preferably 100N / 4cm 2 More than, more preferably 120N / 4cm 2 When the cleavage adhesive strength is within the above preferred range, it is possible to suppress peeling when stress in the cleavage direction is applied to an adherend fixed by the pressure-sensitive adhesive sheet. The split adhesive strength of the pressure-sensitive adhesive sheet can be confirmed, for example, by the method described in "Evaluation of split adhesive strength" in the examples described later.

[0139] <Average thickness of adhesive sheet> The average thickness of the adhesive sheet is not particularly limited and can be appropriately selected based on the average thickness of the adhesive layer and the substrate layer. It is preferably 15 μm to 800 μm, more preferably 30 μm to 540 μm, further preferably 60 μm to 320 μm, and particularly preferably 70 μm to 250 μm. It should be noted that in the present specification, the "average thickness of the adhesive layer" refers to the thickness of the adhesive layer at 5 positions at intervals of 100 mm in the width direction of the above-mentioned adhesive sheet in the length direction, and in each of the above-mentioned cut surfaces, using a TH-104 paper / film thickness measuring machine (manufactured by TESTER SANGYO Co., Ltd.) to measure the thickness of the above-mentioned adhesive layer at 5 positions at intervals of 100 mm in the width direction, and the average value of the thickness of a total of 25 positions obtained.

[0140] <Average width of adhesive sheet> The average width of the adhesive sheet is not particularly limited and can be appropriately selected according to the purpose of use, and is preferably 1 mm to 3000 mm, more preferably 50 mm to 2500 mm, and further preferably 400 mm to 2500 mm. The average width of the adhesive sheet can be appropriately adjusted according to the object of attachment when the adhesive sheet is used for fixing, etc. It should be noted that in this specification, "the average width of the substrate layer" refers to the average value of the total width of five locations obtained by measuring the width of the above-mentioned substrate layer at five locations at intervals of 100 mm in the length direction using a known gauge such as a ruler, a tape measure, or a convex tape measure.

[0141] <Method for producing adhesive sheet> As a method for manufacturing the above-mentioned adhesive sheet, there is no particular limitation as long as it has the above-mentioned adhesive layer and the above-mentioned base layer, and it can be appropriately selected from known methods, preferably including an adhesive layer forming step, a base layer forming step and a laminating step, and further including other layer forming steps as needed. In addition, it can also be manufactured by a multi-layer simultaneous forming step of simultaneously performing the above-mentioned adhesive layer forming step and the above-mentioned base layer forming step.

[0142] <<Adhesive layer forming step>> The adhesive layer forming step is not particularly limited as long as the adhesive layer can be formed, and may be appropriately selected depending on the purpose. For example, the same method as described in the above “〈〈Adhesive layer forming method〉〉” may be mentioned, and preferred aspects are also the same.

[0143] <<Base material layer forming step>> The substrate layer forming step is not particularly limited as long as the substrate layer can be formed, and may be appropriately selected depending on the purpose. For example, the same method as described in the above “<<Method for forming substrate layer>>” may be mentioned, and the preferred aspects are also the same.

[0144] <<Lamination process>> The lamination step is a step of laminating the substrate layer with the adhesive layer. There is no particular limitation on the method of laminating the substrate layer with the adhesive layer, and the method can be appropriately selected from known methods, such as a method of laminating the substrate layer with the adhesive layer under pressure.

[0145] The above-mentioned adhesive sheet can be easily stretched and peeled off even if the stretching direction is perpendicular to the attachment surface of the attachment object, and is not easy to tear even when the thickness of the base material of the adhesive sheet is thin. It is excellent in impact resistance, shear adhesion and cleavage adhesion. Therefore, it can be suitable for fixing sheet metals to each other that constitute larger electronic devices such as thin-film televisions, home appliances, OA equipment, fixing exterior parts and frames, fixing rigid parts such as exterior parts and batteries on smaller electronic devices such as portable electronic terminals, cameras, personal computers, etc., and temporary fixing of the parts, as well as labels displaying product information. [Example]

[0146] Hereinafter, the present invention will be specifically described with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples at all.

[0147] In the production of adhesive sheets 1 to 16 of Examples 1 to 11 and Comparative Examples 1 to 6 below, the following compositions were used as the resin compositions (1) to (5) in the substrate layer and the adhesive compositions (1) to (12) in the adhesive layer.

[0148] <Resin composition (1)> The resin composition (1) is a mixture of a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer (hereinafter sometimes referred to as "SIS"), wherein the structural unit derived from styrene represented by the following chemical formula (1) is 25% by weight and the ratio of the styrene-isoprene copolymer to the total amount of the resin composition (1) is 17% by weight.

[0149]

Chemical formula 2

[0150] <Resin composition (2)> As the resin composition (2), an ester polyurethane compound (Mobilon Film MF100T, manufactured by Nisshinbo Textile Co., Ltd.) was used.

[0151] <Resin composition (3)> The resin composition (3) is a mixture of a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer (SIS), wherein the structural unit derived from styrene represented by the chemical formula (1) is 15 wt % and the ratio of the styrene-isoprene copolymer to the total amount of the resin composition (3) is 12 wt %.

[0152] <Resin composition (4)> The resin composition (4) is a mixture of a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer (SIS), wherein the structural unit derived from styrene represented by the chemical formula (1) is 15 wt % and the ratio of the styrene-isoprene copolymer to the total amount of the resin composition (4) is 80 wt %.

[0153] <Resin composition (5)> As the resin composition (5), a PET film (Lumirror (registered trademark) S10, thickness 100 μm, manufactured by Toray Industries, Inc.) was used.

[0154] <Preparation of Adhesive Composition (1)> In a reaction vessel equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer and a dropping funnel, 75.94 parts by weight of n-butyl acrylate, 5 parts by weight of 2-ethylhexyl acrylate, 15 parts by weight of cyclohexyl acrylate, 4 parts by weight of acrylic acid, 0.06 parts by weight of 4-hydroxybutyl acrylate and 200 parts by weight of ethyl acetate were added, and the mixture was heated to 65° C. while nitrogen was blown in under stirring to obtain a mixture (1). Next, 4 parts by weight of a 2,2'-azobisisobutyronitrile solution (solid content 2.5% by weight) dissolved in ethyl acetate in advance was added to the mixture (1), and the mixture was kept at 65° C. for 10 hours under stirring to obtain a mixture (2). Next, the mixture (2) was diluted with 98 parts by weight of ethyl acetate and filtered through a 200-mesh metal mesh to obtain an acrylic copolymer solution (1) having a weight average molecular weight of 1.6 million (polystyrene conversion). Next, 5 parts by weight of a polymerized rosin ester tackifier resin (D-125, manufactured by Arakawa Chemical Industries, Ltd.) and 15 parts by weight of a petroleum tackifier resin (FTR (registered trademark) 6125, manufactured by Mitsui Chemicals, Inc.) were mixed and stirred with 100 parts by weight of the acrylic copolymer solution (1), and then ethyl acetate was added to obtain a binder resin solution (1) having a solid content of 31% by weight. Next, 30 parts by weight of filler 1 (aluminum hydroxide, polygonal, BW153, manufactured by Nippon Light Metal Co., Ltd., volume average particle size: 18 μm, particle size distribution (D 90 / D 10 ): 12.3), then, with respect to 100 parts by weight of the above-mentioned adhesive resin solution (1), 1.3 parts by weight of a crosslinking agent (BURNOCK D-40, manufactured by DIC Corporation; a trimethylolpropane adduct of toluene diisocyanate, with an isocyanate group content of 7% by weight and a non-volatile component of 40% by weight) is added, and the mixture is stirred and mixed to make it uniform, thereby obtaining an adhesive composition (1). It should be noted that the particle size distribution (D 90 / D 10 ) is a value obtained by measuring the particle size of the filler particles using a measuring machine (Microtrac) using a laser diffraction scattering method and converting it into a particle size distribution.

[0155] <Preparation of Adhesive Composition (2)> In the above “Preparation of Adhesive Composition (1)”, Adhesive Composition (2) was prepared by the same method as in the above “Preparation of Adhesive Composition (1)” except that the type and addition amount of filler were changed to the type and addition amount shown in the following Table 1. Note that filler 2 is nickel powder (Type 123, manufactured by Inco, polygonal, volume average particle size: 11.9 μm), and the particle size distribution (D 90 / D 10 ) is 4.2.

[0156] <Preparation of Adhesive Composition (3)> In the above “Preparation of Adhesive Composition (1)”, Adhesive Composition (3) was prepared by the same method as in the above “Preparation of Adhesive Composition (1)” except that the type of filler was changed to the type shown in Table 2 below. It should be noted that filler 3 is aluminum hydroxide (B303, manufactured by Nippon Light Metal Co., Ltd., polygonal, volume average particle size: 23 μm), and the particle size distribution (D 90 / D 10 ) is 18.5.

[0157] <Preparation of Adhesive Composition (4)> In the above “Preparation of Adhesive Composition (1)”, Adhesive Composition (4) was prepared by the same method as in the above “Preparation of Adhesive Composition (1)” except that the type of filler was changed to the type shown in Table 2 below. It should be noted that filler 4 is aluminum hydroxide (BE033, manufactured by Nippon Light Metal Co., Ltd., polygonal, volume average particle size: 3 μm), and the particle size distribution (D 90 / D 10 ) is 5.8.

[0158] <Preparation of Adhesive Composition (5)> In the above “Preparation of Adhesive Composition (1)”, Adhesive Composition (5) was prepared by the same method as in the above “Preparation of Adhesive Composition (1)” except that the addition amount of the filler was changed to the addition amount shown in Table 2 below.

[0159] <Preparation of Adhesive Composition (6)> In the above “Preparation of Adhesive Composition (1)”, Adhesive Composition (6) was prepared by the same method as in the above “Preparation of Adhesive Composition (1)” except that the addition amount of the filler was changed to the addition amount shown in Table 2 below.

[0160] <Preparation of Adhesive Composition (7)> In a reaction container equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer and a dropping funnel, 97.97 parts by weight of n-butyl acrylate, 2.0 parts by weight of acrylic acid, 0.03 parts by weight of 4-hydroxybutyl acrylate and 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator were dissolved in a solvent containing 100 parts by weight of ethyl acetate, and polymerization was carried out at 70°C for 12 hours to obtain an acrylic copolymer solution (2) having a weight average molecular weight of 2,000,000 (in terms of polystyrene). Next, 25 parts by weight of a glycerol ester of disproportionated rosin (SUPERESTER A100, manufactured by Arakawa Chemical Industries, Ltd.), 5 parts by weight of a pentaerythritol ester of polymerized rosin (Pensel D135, manufactured by Arakawa Chemical Industries, Ltd.), and 20 parts by weight of a styrene-based petroleum resin (FTR (registered trademark) 6100, manufactured by Mitsui Chemicals, Inc.) were added to 100 parts by weight of the acrylic copolymer solution (2), and ethyl acetate was added and uniformly mixed to obtain a binder solution (2) having a solid content of 31% by weight. Next, 30 parts by weight of filler 1 (aluminum hydroxide, BW153, manufactured by Nippon Light Metal Co., Ltd., volume average particle size: 18 μm, particle size distribution (D 90 / D 10 ): 12.3), then, with respect to 100 parts by weight of the above-mentioned adhesive resin solution (2), 1.3 parts by weight of an isocyanate crosslinking agent (Coronate L-45, manufactured by Nippon Polyurethane Industries, Ltd., 45% by weight of non-volatile components) are added, and the mixture is stirred and mixed to make it uniform, thereby obtaining an adhesive composition (7).

[0161] <Preparation of Adhesive Composition (8)> In the above “Preparation of Adhesive Composition (1)”, Adhesive Composition (12) was prepared by the same method as in the above “Preparation of Adhesive Composition (1)” except that the type of filler was changed to the type shown in Table 2 below. Note that filler 5 is silicone particles (KMP-601, manufactured by Shin-Etsu Chemical Co., Ltd., spherical, volume average particle size: 12 μm), and the particle size distribution (D 90 / D 10 ) is 4.4.

[0162] <Preparation of Adhesive Composition (9)> An adhesive composition (9) was prepared by the same method as in the above “Preparation of adhesive composition (1)” except that no filler was added in the above “Preparation of adhesive composition (1)”.

[0163] <Preparation of Adhesive Composition (10)> In the above “Preparation of Adhesive Composition (1)”, Adhesive Composition (10) was prepared by the same method as in the above “Preparation of Adhesive Composition (1)” except that the addition amount of the filler was changed to the addition amount shown in Table 3 below.

[0164] <Preparation of Adhesive Composition (11)> In the above “Preparation of Adhesive Composition (1)”, Adhesive Composition (11) was prepared by the same method as in the above “Preparation of Adhesive Composition (1)” except that the addition amount of the filler was changed to the addition amount shown in Table 3 below.

[0165] <Preparation of Adhesive Composition (12)> In the above “Preparation of Adhesive Composition (1)”, Adhesive Composition (12) was prepared by the same method as in the above “Preparation of Adhesive Composition (1)” except that the addition amount of the filler was changed to the addition amount shown in Table 3 below.

[0166] (Example 1: Production of Adhesive Sheet (1)) The adhesive composition (1) was applied onto a release liner (VinaFilm 75E-0010GT, manufactured by Fujimori Industries, Ltd., hereinafter the same) using an applicator to a thickness of 50 μm after drying, and dried at 80° C. for 3 minutes to prepare an adhesive layer. Next, toluene was added to the resin composition (1), stirred to make it uniform, applied on the release liner with an applicator to a thickness of 50 μm after drying, and dried at 60° C. for 5 minutes to prepare a base layer. After the release liner of the substrate layer was peeled off, the adhesive layer from which the release liner was peeled off was attached to both surfaces of the substrate layer, and the laminated structure of the substrate layer and the adhesive layer was pressed at 0.2 MPa to produce an adhesive sheet (1).

[0167] (Example 2: Production of Adhesive Sheet (2)) In the production of the pressure-sensitive adhesive sheet (1) of Example 1, a pressure-sensitive adhesive sheet (2) was produced in the same manner as in Example 1 except that the thickness of the substrate layer and the thickness of the pressure-sensitive adhesive layer were changed to the conditions described in Table 1.

[0168] (Example 3: Production of Adhesive Sheet (3)) In the production of the PSA sheet (1) of Example 1, a PSA sheet (3) was produced in the same manner as in Example 1 except that the thickness of the substrate layer, the type of the PSA composition, and the thickness of the PSA layer were changed to the conditions described in Table 1.

[0169] (Example 4: Production of Adhesive Sheet (4)) In the production of the adhesive sheet (1) of Example 1, an adhesive sheet (4) was produced in the same manner as in Example 1 except that the type of the resin composition in the substrate layer, the thickness of the substrate layer, and the thickness of the adhesive layer were changed to the conditions described in Table 1.

[0170] (Example 5: Production of Adhesive Sheet (5)) In the production of the pressure-sensitive adhesive sheet (1) of Example 1, a pressure-sensitive adhesive sheet (5) was produced by the same method as in Example 1 except that the type of the resin composition in the substrate layer was changed to the conditions described in Table 1.

[0171] (Example 6: Production of Adhesive Sheet (6)) In the production of the PSA sheet (1) of Example 1, a PSA sheet (6) was produced in the same manner as in Example 1 except that the thickness of the substrate layer, the type of the PSA composition, and the thickness of the PSA layer were changed to the conditions described in Table 2.

[0172] (Example 7: Production of Adhesive Sheet (7)) In the production of the pressure-sensitive adhesive sheet (1) of Example 1, a pressure-sensitive adhesive sheet (7) was produced by the same method as in Example 1 except that the type of the pressure-sensitive adhesive composition was changed to the conditions described in Table 2.

[0173] (Example 8: Production of Adhesive Sheet (8)) In the production of the PSA sheet (1) of Example 1, a PSA sheet (8) was produced in the same manner as in Example 1 except that the type of the PSA composition and the thickness of the PSA layer were changed to the conditions described in Table 2.

[0174] (Example 9: Production of Adhesive Sheet (9)) In the production of the PSA sheet (1) of Example 1, a PSA sheet (9) was produced in the same manner as in Example 1 except that the type of the PSA composition and the thickness of the PSA layer were changed to the conditions described in Table 2.

[0175] (Example 10: Production of Adhesive Sheet (10)) In the production of the PSA sheet (1) of Example 1, a PSA sheet (10) was produced in the same manner as in Example 1 except that the type of the PSA composition and the thickness of the PSA layer were changed to the conditions described in Table 2.

[0176] (Example 11: Production of Adhesive Sheet (11)) In the production of the PSA sheet (1) of Example 1, a PSA sheet (11) was produced in the same manner as in Example 1 except that the type of the PSA composition and the thickness of the PSA sheet were changed to the conditions described in Table 2.

[0177] (Comparative Example 1: Production of Pressure-Sensitive Adhesive Sheet (12)) The adhesive composition (1) was applied onto the release liner using an applicator to a thickness of 25 μm after drying, and dried at 80° C. for 3 minutes to prepare an adhesive layer. The adhesive layer from which the release liner was peeled off was attached to both surfaces of a PET film (the resin composition (5)) as a substrate layer, and the laminated structure of the substrate layer and the adhesive layer was pressed at 0.2 MPa to produce an adhesive sheet (12).

[0178] (Comparative Example 2: Production of Pressure-Sensitive Adhesive Sheet (13)) In the production of the adhesive sheet (1) of Example 1, an adhesive sheet (13) was produced in the same manner as in Example 1 except that the type of the resin composition in the substrate layer, the thickness of the substrate layer, and the thickness of the adhesive layer were changed to the conditions described in Table 3.

[0179] (Comparative Example 3: Production of Pressure-Sensitive Adhesive Sheet (14)) In the production of the PSA sheet (1) of Example 1, a PSA sheet (14) was produced in the same manner as in Example 1 except that the thickness of the substrate layer, the type of the PSA composition, and the thickness of the PSA layer were changed to the conditions described in Table 3.

[0180] (Comparative Example 4: Production of Pressure-Sensitive Adhesive Sheet (15)) In the production of the adhesive sheet (1) of Example 1, an adhesive sheet (15) was produced in the same manner as in Example 1 except that the thickness of the substrate layer, the type of the adhesive composition, and the thickness of the adhesive layer were changed to the conditions described in Table 3.

[0181] (Comparative Example 5: Production of Pressure-Sensitive Adhesive Sheet (16)) In the production of the PSA sheet (1) of Example 1, a PSA sheet (16) was produced in the same manner as in Example 1 except that the thickness of the substrate layer, the type of the PSA composition, and the thickness of the PSA layer were changed to the conditions described in Table 3.

[0182] (Comparative Example 5: Production of Adhesive Sheet (17)) In the production of the adhesive sheet (1) of Example 1, an adhesive sheet (17) was produced in the same manner as in Example 1 except that the thickness of the substrate layer, the type of the adhesive composition, and the thickness of the adhesive layer were changed to the conditions described in Table 3.

[0183] The stress, breaking stress and breaking elongation of the adhesive sheets (1) to (17) of Examples 1 to 11 and Comparative Examples 1 to 6 and their substrate layers and adhesive layers at 25% elongation were measured by the following methods. In addition, the hardness (Shore A) of the adhesive sheets (1) to (17) of Examples 1 to 11 and Comparative Examples 1 to 6 was also measured by the following method. In addition, the volume ratio of the filler in the adhesive layer of the adhesive sheets (1) to (17) of Examples 1 to 11 and Comparative Examples 1 to 6 was also measured by the following method.

[0184] <<Measurement of stress, breaking stress and breaking elongation at 25% elongation of adhesive sheet or substrate layer>> Each adhesive sheet or each substrate layer was punched into a dumbbell shape with a line length of 20 mm and a width of 6 mm, and stretched in the longitudinal direction at a stretching speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measurement atmosphere of 23°C and 50% RH, thereby measuring the stress, breaking stress and breaking elongation of each adhesive sheet or each substrate layer when stretched by 25%. The results are shown in the following Tables 1 to 3.

[0185] <<Measurement of stress at 25% elongation, breaking stress, and breaking elongation of adhesive layer>> Each adhesive layer was punched into a dumbbell shape with a line length of 20 mm and a width of 10 mm, and stretched in the longitudinal direction at a stretching speed of 300 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measurement atmosphere of 23°C and 50% RH, thereby measuring the stress, breaking stress and breaking elongation of each adhesive layer when the elongation is 25%. The results are shown in the following Tables 1 to 3.

[0186] <<Measurement of hardness>> The Shore A hardness of each PSA sheet was measured in accordance with JIS K 6253 using a durometer (spring type rubber durometer) (Model: GS-719G, manufactured by TECLOCK CO., LTD.).

[0187] <<Measurement of volume ratio of filler particles in adhesive layer>> The volume ratio of the filler in the adhesive layer was calculated according to the following formulas (1) to (3). Weight of binder resin A (g) / density of binder resin A (g / cm 3 ) = Volume of binder resin A (cm 3 )···Formula (1) Weight of filler particles B (g) / density of filler particles B (g / cm 3 ) = volume of filler particles B (cm 3 )···Formula (2) [Volume of filler particles B (cm 3 ) / (volume of binder resin A(cm 3 ) + volume of filler particles B (cm 3 ))] × 100 = volume ratio of filler particles (%) ···Formula (3) The density A of the binder resin was set to 1.2 g / cm 3 As the density B of the filler particles, the density of aluminum hydroxide is 2.42 g / cm 3 , the density of nickel is 8.90g / cm 3 The density of silicone particles is 0.98 g / cm 3 Calculated in the way.

[0188] The removability (perpendicular tensile peeling), impact resistance, 180° peeling strength, shearing strength and cleavage strength of the PSA sheets (1) to (17) of Examples 1 to 11 and Comparative Examples 1 to 6 were tested and evaluated by the following methods. The evaluation results are shown in Tables 1 to 3 below.

[0189] <<Evaluation of removability (perpendicular direction tensile peeling)>> Each adhesive sheet was cut into pieces of 60 mm in length and 10 mm in width. The pieces of 10 mm in length and 10 mm in width were used as grippers. In the exposed state, a clean and smooth aluminum plate (length 150 mm, width 50 mm, thickness 2 mm, alloy number A1050) was attached to one side of the adhesive sheet at an atmosphere of 23°C and 50% RH. Next, a clean and smooth acrylic plate (length 150 mm, width 50 mm, thickness 2 mm, Acrylite L, color tone: colorless, manufactured by Mitsubishi Rayon Co., Ltd.) was attached to the surface opposite to the surface of the adhesive sheet to which the aluminum plate was attached. A load of 5 kg was applied to the laminated structure of the aluminum plate, the adhesive sheet and the acrylic plate, and the laminated structure was crimped by reciprocating pressure with a roller once. The laminated structure was then left to stand for 3 days at an atmosphere of 23°C and 50% RH to serve as a test piece. Under the conditions of 23°C and 50% RH, the grip portion of the adhesive sheet in the test piece was stretched at a speed of 300 mm / min in a direction of 90° (vertical direction) relative to the attached surface of the adhesive sheet using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.). At this time, the occurrence of tearing of the adhesive sheet and the degree of residual adhesive composition on the adherend (at least one of the aluminum plate and the acrylic plate) after the adhesive sheet was peeled off were visually confirmed. The test according to the above method was performed three times, and the removability (perpendicular direction tensile peeling) was evaluated based on the following evaluation criteria. The results are shown in Tables 1 to 3 below. [Evaluation criteria] ⊚: The tearing of the pressure-sensitive adhesive sheet occurred 0 times out of 3 times. ○: The PSA sheet was torn once out of three times, and / or the area of ​​the PSA composition remaining on the adherend was less than 1 / 5 of the initial attachment area. △: The PSA sheet was torn once out of three times, the PSA sheet was not stretched, and the area of ​​the PSA sheet remaining on the adherend was 4 / 5 or more of the initial attachment area. ×: The PSA sheet was torn 2 or more times out of 3 times, and / or the PSA sheet did not stretch and could not be peeled off. It should be noted that ◎ and ○ are evaluation criteria for indicating no problem in use.

[0190] <<Evaluation of impact resistance>> Each adhesive sheet was cut into pieces with a length of 20 mm and a width of 5 mm, and two pieces were prepared. Figure 1 As shown in FIG. 1 , the adhesive sheet 1 is attached in parallel to an acrylic plate 2 (length 50 mm, width 50 mm, thickness 2 mm, Acrylite L, color tone: colorless, manufactured by Mitsubishi Rayon Co., Ltd.) at a distance of 40 mm. Figure 2 As shown, an acrylic plate 2 to which the above-mentioned adhesive sheet 1 is attached is attached to the central part of an ABS plate (length 150 mm, width 100 mm, thickness 2 mm, TAFACE R, manufactured by Sumitomo Bakelite Co., Ltd., color: natural, no wrinkles) 3, and a load of 2 kg is applied to the laminated structure of the above-mentioned acrylic plate 2, the above-mentioned adhesive sheet 1 and the above-mentioned ABS plate 3 while reciprocatingly pressurizing them once with a roller to make them pressed together. Then, the laminated structure is left to stand for 24 hours at an atmosphere of 40°C and 50% RH to serve as a test piece. like Figure 3As shown in FIG. 1 , a U-shaped measuring table (aluminum, 150 mm in length, 100 mm in width, 45 mm in height, and 5 mm in thickness) 4 is set on the base of a DuPont impact tester (manufactured by TESTER SANGYO Co., Ltd.), and the above-mentioned test piece is placed on it so that the acrylic plate 2 in the test piece faces downward ( Figure 3 ). Under the conditions of atmosphere 23°C and 50% RH, a stainless steel impact core (25 mm in diameter and 300 g in weight) 5 was dropped from the side of the ABS plate 3 to the center of the ABS plate 3. At this time, the height of the impact core 5 was changed from 10 cm to 10 cm at a time, and the impact core 5 was dropped 5 times at 10 second intervals for each height. The height at which the peeling or destruction of the adhesive sheet in the test piece was confirmed was measured, and the impact resistance was evaluated based on the following evaluation criteria. The results are shown in the following Tables 1 to 3. [Evaluation criteria] ⊚: When the impact core 5 was dropped from a height of 60 cm or more, the pressure-sensitive adhesive sheet was not peeled off or broken. ○: When the impact core 5 was dropped from a height of 30 cm to 50 cm, the pressure-sensitive adhesive sheet was not peeled off or broken. △: When the impact core 5 was dropped from a height of 10 cm or more and less than 30 cm, the pressure-sensitive adhesive sheet was peeled off or broken. ×: When the height of the impact core 5 reached 10 cm, the adhesive sheet was peeled off or broken. It should be noted that ◎ and ○ are evaluation criteria for indicating no problem in use.

[0191] <<Evaluation of 180° peel adhesion>> The 180° peeling adhesion was measured in accordance with JIS Z 0237. Specifically, each adhesive sheet was cut into pieces of 150 mm in length and 20 mm in width, and a PET film of 25 μm in thickness was used for lining on one side of the adhesive sheet. Next, the other side of the adhesive sheet was attached to a stainless steel plate (100 mm in length, 30 mm in width, and 3 mm in thickness) under the conditions of an atmosphere of 23° C. and 50% RH, and the laminated structure of the adhesive sheet and the stainless steel plate was pressed once by reciprocating pressure with a roller while applying a load of 2 kg, and then left to stand for 1 hour under the conditions of an atmosphere of 23° C. and 50% RH to serve as a test piece. The PSA sheet in the test piece was stretched in the 180° direction (horizontal direction) at a rate of 300 mm / min at an atmosphere of 23°C and 50% RH using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) to measure the 180° peel adhesion of the PSA sheet.

[0192] <<Evaluation of shear adhesion>> Each adhesive sheet was cut into a length of 20 mm and a width of 20 mm. Under the conditions of an atmosphere of 23°C and 50% RH, one side of the adhesive sheet was attached to the surface of a clean stainless steel plate A (length 100 mm, width 30 mm, thickness 3 mm) that had been subjected to a grain-grinding treatment using water-resistant abrasive paper (No. 360) so that the attached area became 20 mm×20 mm. Next, a clean and smooth stainless steel plate B (length 100 mm, width 30 mm, thickness 3 mm) that had been subjected to a grain-grinding treatment using water-resistant abrasive paper (No. 360) was attached to the surface of the adhesive sheet opposite to the surface to which the stainless steel plate A was attached. While applying a load of 5 kg to the laminated structure of the stainless steel plate A, the adhesive sheet and the stainless steel plate B, the laminated structure was pressed once by reciprocating pressure with a roller, and then left to stand for 24 hours under the conditions of an atmosphere of 23°C and 50% RH to serve as a test piece. Under the conditions of 23°C and 50% RH, the stainless steel plate A constituting the test piece was fixed, and the stainless steel plate B constituting the test piece was stretched in the shear direction of the adhesive sheet at a stretching speed of 50 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) to measure the shear adhesive strength. The results are shown in the following Tables 1 to 3.

[0193] <<Evaluation of splitting adhesive strength>> Each adhesive sheet was cut into pieces of 20 mm in length and 20 mm in width. Under the conditions of 23°C and 50% RH, a clean and smooth aluminum plate (alloy number A1050, length 50 mm, width 40 mm, thickness 3 mm) was attached to one side of the adhesive sheet in such a manner that the attachment area became 20 mm × 20 mm. Next, a clean and smooth aluminum plate (alloy number A1050, length 50 mm, width 40 mm, thickness 3 mm) was attached to the surface of the adhesive sheet opposite to the surface to which the aluminum plate was attached. A load of 5 kg was applied to the laminated structure of the two aluminum plates and the adhesive sheet, and the laminated structure was crimped by reciprocating pressure with a roller once, and then left to stand for 24 hours under the conditions of 23°C and 50% RH to serve as a test piece. Under the conditions of 23°C and 50% RH, the aluminum plate A constituting the above test piece was fixed, and the aluminum plate B constituting the above test piece was stretched in the tearing direction (thickness direction) of the adhesive sheet at a pulling speed of 50 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) to measure the tearing adhesive strength. The results are shown in the following Tables 1 to 3.

[0194]

Table 1

[0195]

Table 2

[0196]

Table 3

[0197] According to the results in Tables 1 to 3 above, the adhesive sheets of Examples 1 to 11 can be easily stretched and peeled off even when the stretching direction is perpendicular to the attachment surface of the attachment object, and are not easy to tear even when the thickness of the substrate of the adhesive sheet is thin, and have excellent impact resistance, shear adhesion and cleavage adhesion. On the other hand, the PSA sheets of Comparative Examples 1 to 6 could not be stretched and peeled when the stretching direction was perpendicular to the attachment surface of the attachment object. In addition, Comparative Examples 1, 5, and 6 had poor impact resistance, and Comparative Example 1 had poor shear adhesion.

[0198] As an aspect of the present invention, for example, the following aspects can be mentioned. <1> A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer and a substrate layer, The adhesive layer contains filler particles and an adhesive resin, wherein the content of the filler particles in the adhesive layer is 10 to 90 parts by weight relative to 100 parts by weight of the adhesive resin, and the volume ratio of the filler particles to the adhesive layer is 4% to 40%. The stress of the adhesive sheet when it is elongated by 25% is 0.15 MPa to 82 MPa. <2> The PSA sheet according to <1>, wherein the particle size distribution (D 90 / D 10 ) is 2.5~20. <3> The pressure-sensitive adhesive sheet according to any one of <1> to <2>, wherein the pressure-sensitive adhesive sheet has a Shore A hardness of 10 to 90. <4> The PSA sheet according to any one of <1> to <3>, wherein the PSA sheet has an elongation at break (MD) of 1000% to 1800%. Industrial Applicability

[0199] The above-mentioned adhesive sheet can be easily stretched and peeled off even if the stretching direction is perpendicular to the attachment surface of the attachment object, and is not easy to tear even when the thickness of the base material of the adhesive sheet is thin. It is excellent in impact resistance, shear adhesion and cleavage adhesion. Therefore, it can be suitable for fixing sheet metals to each other that constitute larger electronic devices such as thin-film televisions, home appliances, OA equipment, fixing exterior parts and frames, fixing rigid parts such as exterior parts and batteries on smaller electronic devices such as portable electronic terminals, cameras, personal computers, etc., and temporary fixing of the parts, as well as labels displaying product information. Description of Reference Numerals

[0200] 1: Adhesive sheet 2: Acrylic board 3: ABS board 4: U-shaped measuring table 5: Impact core.

Claims

1. An adhesive sheet, characterized in that: having an adhesive layer and a substrate layer, The adhesive layer contains filler particles and an adhesive resin, The content of the filler particles in the adhesive layer is 10 parts by weight to 90 parts by weight relative to 100 parts by weight of the binder resin. The volume ratio of the filler particles to the adhesive layer is 4% to 40%, The stress of the substrate layer when it is elongated by 25% is 0.2MPa to 2.0MPa. The stress of the adhesive sheet when it is elongated by 25% is 0.15Mpa to 82Mpa.

2. The adhesive sheet according to claim 1, wherein The average thickness of the adhesive layer is 40 μm to 110 μm.

3. The adhesive sheet according to claim 1, wherein The base material constituting the base layer is a styrene resin or a polyurethane resin.

4. The adhesive sheet according to claim 1, wherein The substrate material constituting the substrate layer contains a styrene-based resin, and the styrene-based resin includes at least one selected from a linear styrene-based resin, a branched styrene-based resin, and a multi-branched styrene-based resin.

5. The adhesive sheet according to claim 1, wherein The substrate material constituting the substrate layer contains a styrene-based resin including a block copolymer.

6. The adhesive sheet according to claim 5, wherein The block copolymer is a triblock copolymer.

7. The adhesive sheet according to claim 1, wherein The base material constituting the base layer contains a styrene-based resin, and contains at least a styrene-isoprene-styrene copolymer as the styrene-based resin.

8. The adhesive sheet according to claim 7, wherein The base material constituting the base layer contains a styrene-based resin and further contains a styrene-isoprene copolymer as the styrene-based resin.

9. The adhesive sheet according to claim 8, wherein The content of the styrene-isoprene copolymer is 12% by weight to 80% by weight relative to the total weight of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer contained in the styrene-based resin.

10. The adhesive sheet according to claim 1, wherein The particle size distribution of the filler particles is 90 / D 10 It is 2.5 to 20.

11. The adhesive sheet according to claim 1, wherein The ratio of the volume average particle size of the filler particles to the average thickness of the adhesive layer represented by [volume average particle size of filler particles / average thickness of adhesive layer] is 5 / 100 to 95 / 100.

12. The adhesive sheet according to claim 1, wherein The Shore A hardness of the adhesive sheet is 10-90.

13. The adhesive sheet according to claim 1, wherein The shear adhesion of the adhesive sheet is 150N / 4cm 2 Above, the tearing adhesion is 200N / 4cm 2 above.

14. The adhesive sheet according to claim 1, wherein The adhesive sheet has a breaking elongation MD of 1000% to 1800%.

Citation Information

Patent Citations

  • Adhesive tape and tape substrate used therefor

    JP2015124289A

  • Removable pressure-sensitive adhesive strip

    JP2016504449A